Liquid room temperature fluoride ion battery

By using rare earth metal or alkaline earth metal anode, transition metal and shell structure cathode in fluoride ion battery, and forming a solid electrolyte intermediate phase layer on the anode surface, the problem of insufficient stability and energy density of fluoride ion battery at room temperature is solved, and efficient and rechargeable battery performance is achieved.

CN113195464BActive Publication Date: 2025-04-15HONDA MOTOR CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN201980080733.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2019-12-05
Publication Date
2025-04-15
Estimated Expiration
2039-12-05

AI Technical Summary

Technical Problem

Existing fluoride ion batteries lack effective, rechargeable electrolytes and reversible cathode and anode materials at room temperature, and metal nanoparticles are easily soluble in liquid electrolytes, resulting in insufficient stability and energy density.

Method used

An anode containing rare earth metal or alkaline earth metal, a cathode with a transition metal and shell structure, and a liquid fluoride electrolyte are used, and a solid electrolyte interphase layer (SEI layer) is formed on the anode surface to prevent metal from dissolving and expanding the negative potential of the electrolyte.

Benefits of technology

A fluorine ion battery that can be recharged at room temperature is realized, which improves the durability and efficiency of the battery, prevents the dissolution of metal electrodes, and enhances the stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005266595130000031
    Figure FDA0005266595130000031
  • Figure FDA0005266595130000032
    Figure FDA0005266595130000032
  • Figure FDA0005266595130000033
    Figure FDA0005266595130000033
Patent Text Reader

Abstract

The present disclosure relates to fluoride ion batteries and structures of metal-based electrode materials for various fluoride ion batteries. The structures of the metal-based electrode materials contain one or more shells or interfaces that enable the electrodes to operate with liquid electrolytes at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is a continuation-in-part of U.S. patent application No. 15 / 844,079 filed on December 15, 2017, which claims priority to U.S. Provisional Patent Application No. 62 / 453,295 filed on February 1, 2017 and U.S. Provisional Patent Application No. 62 / 434,611 filed on December 15, 2016; this application is a continuation-in-part of U.S. patent application No. 16 / 455,022 filed on June 27, 2019, which is a divisional of U.S. patent application No. 13 / 708,616 filed on December 7, 2012, which claims priority to U.S. Provisional Patent Application No. 61 / 5 filed on December 7, 2011. 67,973; This application is a continuation-in-part application of U.S. patent application No. 16 / 444,854 filed on June 18, 2019, which claims priority to U.S. Provisional Patent Application No. 62 / 775,748 filed on December 5, 2018; This application claims priority to U.S. Provisional Patent Application No. 62 / 775,748 filed on December 5, 2018; This application is a continuation-in-part application of U.S. Patent Application No. 16 / 013,739 filed on June 20, 2018, which claims priority to U.S. Provisional Patent Application No. 62 / 676,693 filed on May 25, 2018, and is a continuation-in-part application of ... 15 / 844,079, filed on December 15, 2016, which claims priority to U.S. Provisional Patent Application No. 62 / 453,295 filed on February 1, 2017 and U.S. Provisional Patent Application No. 62 / 434,611 filed on December 15, 2016; This application claims priority to U.S. Provisional Patent Application No. 62 / 863,114 filed on June 18, 2019; This application is a continuation-in-part application of U.S. Patent Application No. 15 / 228,876 filed on August 4, 2016, which claims priority to U.S. Provisional Patent Application No. 62 / 200,99 filed on August 4, 2015 8; this application is a continuation-in-part application of U.S. Patent Application No. 16 / 702,327 filed on December 3, 2019, which claims priority to U.S. Provisional Application No. 62 / 776,978 filed on December 7, 2018, U.S. Provisional Application No. 62 / 775,690 filed on December 5, 2018, and U.S. Provisional Application No. 62 / 863,114 filed on June 18, 2019; this application claims priority to U.S. Provisional Application No. 62 / 776,978 filed on December 7, 2018; and this application claims priority to U.S. Provisional Application No. 62 / 775,690 filed on December 5, 2018. The disclosures of the foregoing applications are hereby incorporated by reference in their entirety.

[0003] STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT

[0004] This invention was made with government support under Grant No. 80NM0018D004 awarded by NASA's Jet Propulsion Laboratory (JPL). This invention was made with government support under Contracts DE-AC05-00OR22725 and DE-AC02-05CH11231 awarded by the U.S. Department of Energy (DOE). The government has certain rights in this invention. Background Art

[0005] Fluoride ion batteries are a novel and underdeveloped alternative next-generation energy storage technology. Fluoride ion batteries can have energy densities much higher than lithium ion batteries. Much of the ongoing research is focused on all-solid-state fluoride ion batteries, which can be charged at elevated temperatures up to a certain level. However, the slow reaction kinetics pose a significant challenge to all-solid-state fluoride ion batteries. The reaction kinetics are better in liquid-type fluoride ion batteries. However, this type of fluoride ion battery still faces many challenges, such as the lack of effective, rechargeable electrolytes and reversible cathode and anode materials at room temperature. Metal nanoparticles are very suitable for use in many applications, including as catalysts and as electrode materials for batteries. However, the use of metal nanoparticles in fluoride ion batteries may be limited due to the dissolution of metals in liquid electrolytes. Preventing dissolution can lead to stable higher energy densities. With the growing energy demand for electric vehicles, portable electronic devices, and portable energy storage, there is a growing demand for advanced fluoride ion batteries with higher energy density. Summary of the invention

[0006] The present disclosure relates to fluoride (F) ion batteries and F shuttle batteries, which may include an anode containing a rare earth metal or an alkaline earth metal (or a mixture of metals) and a solid electrolyte interphase layer; a cathode containing a transition metal and one or more shell (or layer) structures; and a liquid fluoride battery electrolyte. The solid electrolyte interphase (SEI) layer on the anode may include a fluorinated compound. In some embodiments, the SEI layer may include a chemical compound that is stable on the anode surface, such as a reaction derivative formed between a diazonium salt / brine and the anode surface. The present disclosure also relates to a coating, layer or shell used with a cathode comprising a core structure. As used herein, the form of the cathode core is not limited, and it covers structures including but not limited to nanoparticles, nanotubes, nanowires, frames, flakes, nanoporous materials, sheets, films, and foams. In some embodiments, one or more dimensions of the cathode core material can be determined by electronic conductivity or F- ion mobility. In a non-limiting example, 20nm can be the distance limit for F- ion penetration in the core material. In some embodiments, the fluoride ion battery disclosed herein may be a F shuttle battery with multiple electron transfer ( Figure 1A , Figure 2 ). The electrode layers, shells or coatings disclosed herein can prevent the core metals or materials in the anode and cathode from dissolving and / or extending the negative potential of the electrolyte in a liquid electrolyte fluoride ion battery, while enabling efficient charging / discharging at room temperature. The present disclosure also relates to specialized methods for making fluoride ion batteries and various components therein. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] The patent or application file contains at least one drawing executed in color. Copies of the patent or patent application publication with color drawing(s) will be provided by the Office upon request and payment of the fee.

[0008] Figure 1A The energy density of various types of batteries is plotted.

[0009] Figure 1B Examples of suitable anode and cathode metals are depicted.

[0010] Figure 1C A cross-section of a core-shell nanoparticle in one aspect of the present disclosure is shown, the core-shell nanoparticle comprising a core comprising a metal nanoparticle and a shell comprising a metal halide or a metal oxyhalide.

[0011] Figure 2 is a schematic diagram of a fluoride ion electrochemical cell in accordance with one aspect of the present disclosure.

[0012] Figure 3 is a non-limiting schematic diagram showing a solid electrolyte interphase (SEI) layer that allows the passage of ions but not electrons while being stable on the surface of an active material, anode, or current collector, according to some aspects of the present disclosure.

[0013] Figure 4 The reaction (free radical) mechanism of silane (FOTS) with the anode surface in the SEI (solid electrolyte interphase formation) according to some aspects of the present disclosure is shown.

[0014] Figure 5 The reaction (free radical) mechanism of the diazonium salt with the anode surface in the SEI (solid electrolyte interphase formation) according to some aspects of the present disclosure is shown.

[0015] Figure 6 Depicted are the ratio between carbon atoms in the benzene ring of the diazonium molecule and calcium atoms from the electrode (ie, C / Ca ratio) and the ratio between fluoride ions in the diazonium salt and calcium atoms from the electrode (ie, F / Ca ratio) according to some aspects of the present disclosure.

[0016] Figure 7 It is a tetraalkylammonium fluoride salt that decomposes under dry conditions to form HF and HF2 -Schematic diagram of .

[0017] Figure 8 is a bar graph of voltage windows measured from linear sweep voltammograms for non-limiting examples of electrolyte solutions of the present disclosure.

[0018] Fig. 9A and Fig. 9B Depicted is an exemplary improvement in the negative potential of an additive grafted calcium anode in a BTFE-based electrolyte as determined by linear sweep voltammogram (LSV): Fig. 9A )FH-grafted calcium anode in NpMe3NF-BTFE electrolyte; and ( Fig. 9B )FOTS-grafted calcium anode in Et3MeN·BF4-BTFE electrolyte.

[0019] Fig. 10A , 10B and 10C depict exemplary XPS studies of FH SEI and FOTS SEI grafted onto the surface of a calcium anode: Fig. 10A The XPS spectrum of FH SEI grafted on calcium anode is shown; Fig. 10B The XPS spectrum of FOTSSEI grafted on the calcium anode is shown; Fig. 10C The ratio between fluorine and calcium active surface materials (F / Ca) in the SEI layer for FH and FOTS is shown.

[0020] Fig. 10D The fluorination / defluorination of a cerium (Ce) anode with a FOTS SEI layer is shown.

[0021] Fig. 10E pXRD patterns corresponding to pristine Ce, Ce anode with FOTS SEI layer after fluorination (charge), and fluorinated Ce anode after defluorination (discharge) are shown.

[0022] Fig.11 Depicted are exemplary reductions in anode potential (V-window expansion) caused by a SEI layer and anode potentials for several non-limiting anode materials according to aspects of the present disclosure.

[0023] Fig. 12A pXRD characterization of the original powder of copper nanoparticles used for synthesis is shown. α ) spectrum, the characteristic peaks of metallic copper (peaks marked with squares) are depicted.

[0024] Fig. 12B TEM images of synthesized copper nanoparticles (diameter -50 nm) are shown.

[0025] Fig. 12CpXRD characterization of the raw powder of as-synthesized core@shell nanoparticles (Cu@LaF3) is shown. The characteristic peaks of metallic copper (marked with squares) and lanthanum trifluoride (marked with circles) are depicted.

[0026] Fig.13A Cu@LaF3 core-shell nanoparticles and Cu@La 0.97 Ba 0.03 F 2.97 TEM image of core-shell nanoparticles. The inset in the TEM image of Cu@LaF3 nanoparticles is a magnified image of the Cu (core) and LaF3 (shell) regions.

[0027] Fig. 13B Cu@LaF3 and Cu@La before / after fluorination according to some aspects of the present disclosure are shown. 0.97 Ba 0.03 F 2.97 Schematic diagram of nanoparticles. For LaF3 shell and La 0.97 Ba 0.03 F 2.97 Shell F - ions can penetrate Cu by about 5nm and about 10nm respectively. The use of Ba-doped LaF3 shell improves the utilization of Cu because it has higher ionic conductivity compared to LaF3. This calculation is based on Fig.14A The charge / discharge curves in .

[0028] Fig.14A A Cu@LaF3 electrode or a Cu@LaF3 electrode according to some aspects of the present disclosure is shown. 0.97 Ba 0.03 F 2.97 Electrode compared to Ag / Ag + The voltage curve of the first charge-discharge cycle of the reference electrode.

[0029] Fig. 14B The capacity achieved for Cu@LaF3 (9.5% of theoretical capacity) and for Cu@La are shown in accordance with some aspects of the present disclosure. 0.97 Ba 0.03 F 2.97 Comparison of the achieved capacity (18% of the theoretical capacity) and the capacity achieved for CuF2 (theoretical capacity 528 mAh / g).

[0030] Fig.15 Shown is the percentage of energy density achieved by the copper-based F-shuttle cell, normalized by the theoretical capacity of CuF2 (528 mAh / g).

[0031] Fig.16 It shows that LaF3 (Ba doped withx La 1-x F 3-x ) or LaF3 shelled Cu core nanoparticles (diameter ≤ 20 nm), which can be based on Fig.14A The charge / discharge curves in the calculation are fully charged to form CuF2.

[0032] Fig.17 The pXRD spectrum of 6 nm Cu nanoparticles is shown.

[0033] Fig.18 The pXRD spectrum of 6 nm Cu@LaF3 (Cu nanoparticles with LaF3 shell) after initial synthesis is shown. Cu is oxidized to Cu2O.

[0034] Fig.19A TEM images of 6 nm Cu core nanoparticles after initial synthesis are shown.

[0035] Fig.19B TEM image of a 6 nm Cu core with a LaF 3 shell after initial synthesis is shown.

[0036] Fig. 20 Shown is the XRD spectrum of a 6 nm Cu core with a LaF3 shell after reduction of Cu2O. Cu2O is reduced to Cu.

[0037] Fig.21 Shows the La 1-x Ba x F 3-x or LaF3-coated Cu nanowires and cross-sectional views of Cu and fluorinated Cu nanowires.

[0038] Fig. 22 According to some aspects of the present disclosure, Cu nanowires (without La) having a cross-sectional diameter of about 20 nm or less are shown. 1-x Ba x F 3-x or LaF3 coating).

[0039] Fig.23A and Fig. 23B Cu nanowires with a cross-sectional diameter of about 20 nm (without La 1-x Ba x F 3-x or LaF3 coating).

[0040] Fig.24 XRD spectra of Cu nanowires (diameter about 20 nm or less), a small amount of Cu2O after shell formation, and a LaF3 shell of the Cu nanowires are shown according to some aspects of the present disclosure.

[0041] Fig.25A Shown is an SEM image of Cu nanowires after initial synthesis and before two-phase shell formation according to some aspects of the present disclosure.

[0042] Fig.25B SEM images showing the formation of a two-phase LaF 3 shell on Cu nanowires according to some aspects of the present disclosure.

[0043] Fig.26A , 26B 26C and 26C show TEM images of LaF3 formation on / around Cu nanowires at different magnifications / resolutions according to some aspects of the present disclosure.

[0044] Fig. 27 Voltage curves of charge-discharge cycles of an electrode made of Cu nanowires encapsulated in a LaF 3 shell (CuNW@LaF 3 ) according to some aspects of the present disclosure are shown.

[0045] Fig.28 Shown are XRD spectra of CuNW@LaF3 under initial conditions, after charging (fluorination, “F”), and subsequent discharge (defluorination, “deF”) according to some aspects of the present disclosure.

[0046] Fig.29 Shown are voltage curves of charge-discharge cycles of an electrode made of Cu nanowires (average diameter of about 20 nm or less) encapsulated in a soft shell (surfactant shell), according to some aspects of the present disclosure.

[0047] Fig.30 Shown are XRD spectra of CuNW@soft shell (surfactant shell) after charging (fluorination) and after subsequent discharge (defluorination) according to some aspects of the present disclosure. Fig.30 The average diameter of the Cu nanowires measured in is about 20 nm or less.

[0048] Fig.31 Shows the La 1-x Ba x F 3-x or LaF3-coated Cu nanotubes and cross-sectional views of Cu and fluorinated Cu nanotubes.

[0049] Fig.32 Shows the La 1-x Ba x F 3-x Or LaF3-coated Cu nanosheets and designed structures of Cu nanosheets. The minimum thickness of these structures is no more than 20nm.

[0050] Fig.33Shows the La 1-x Ba x F 3-x The hollow Cu nanoframe structure of the LaF3 coating is designed. The thickness of the inner copper wall in the Cu nanoframe is not more than 20nm.

[0051] Fig.34 The comparison of the voltage curves of the charge-discharge cycle of various electrodes is depicted. The electrodes in the figure are composed of about 50nm CuNP@LaF3, about 50nm CuNP@La 0.97 Ba 0.03 F 2.97 , CuNW@LaF3 with a diameter of about 20nm and CuNW@soft shell with a diameter of about 20nm.

[0052] Fig.35 According to some aspects of the present disclosure, for about 50nm CuNP@LaF3, about 50nm CuNP@La 0.97 Ba 0.03 F 2.97 , CuNW@LaF3 with a diameter of about 20nm, CuNW@soft shell with a diameter of about 20nm and the theoretical capacity of CuF2.

[0053] Fig.36 The results show that the CuNP@LaF3 with a diameter of about 50nm and the CuNP@La 0.97 Ba 0.03 F 2.97 The percentage capacity achieved by CuNW@LaF3 with a diameter of about 20 nm and CuNW@soft shell with a diameter of about 20 nm, the percentage capacity is normalized by the theoretical capacity of CuF2 (528 mAh / g).

[0054] Fig.37A Exemplary electrochemically active structures according to some aspects of the present disclosure are shown.

[0055] Fig.37B Exemplary electrochemically active structures according to various aspects of the present disclosure are shown.

[0056] Fig.37C Exemplary electrochemically active structures according to aspects of the present disclosure are shown.

[0057] Fig.38 An exemplary schematic diagram of charging and discharging an electrochemically active structure according to aspects of the present disclosure is shown.

[0058] Fig.39 A general route to obtain a cathode "yolk-shell" complex using a sacrificial inorganic "intermediate" layer is depicted.

[0059] Fig.40 A route to obtain a cathode "yolk-shell" complex using a sacrificial polymer "intermediate" layer is depicted.

[0060] Fig.41 An alternative route to obtain a cathodic "yolk-shell" complex in the absence of a sacrificial "intermediate" layer is depicted.

[0061] Fig.42 A variation of the "sacrificial" synthesis of a cathode "yolk-shell" complex is depicted, in which nanoparticles of the active material are grown on the surface of the "sacrificial" material.

[0062] Fig.43 Depicted is the (cathodic) growth of active material within the internal structure or pores of a preformed "sacrificial" material.

[0063] Fig.44 The growth of (cathodic) active material into the internal structure or pores of a preformed "sacrificial" material is depicted, wherein the shell component is selected to be electrochemically inactive at the electrochemical reaction potential of interest.

[0064] Fig.45 According to some aspects of the present disclosure, the initial 50 nm diameter Cu@LaF3 and Cu@Ba x La 1-x F 3-x Nanoparticles and fluorinated Cu@LaF3 and Cu@Ba x La 1-x F 3-x The illustrative dimensions of are shown. The Ba-doped LaF3 shell has higher ionic conductivity than LaF3, so fluoride ions can penetrate deeper into the Cu core (>3nm) to form more CuF2 during fluorination. Optimizing the Ba-doped shell can effectively utilize the Cu core to increase its actual capacity, ideally close to the theoretical capacity of 528mAh / g.

[0065] Fig.46 Cu@LaF3 and Cu@La according to some aspects of the present disclosure are shown. 0.97 Ba 0.03 F 2.97 XRD spectrum of . DETAILED DESCRIPTION

[0066] The present disclosure relates to fluoride ion batteries and components of fluoride ion batteries. Various aspects of durability and efficiency of components of fluoride ion batteries when using liquid non-aqueous fluoride electrolytes to achieve room temperature rechargeable fluoride ion batteries are disclosed herein.

[0067] Fluoride ion batteries and F shuttle batteries can provide higher energy density than lithium ion batteries (Figure 1), but due to the high energy density and ionic strength of liquid fluoride electrolytes, for example, the metal electrodes in fluoride (F) ion batteries and F shuttle batteries can be easily dissolved in liquid electrolytes. Electrode structures comprising a metal material core and a protective shell (or layer) made of an ion conductor have been studied to protect the metal material from dissolution. In the present disclosure, a protective shell or layer material is provided, which can protect the electrode core material from dissolution while providing electrode functionality (e.g., charging / discharging at room temperature).

[0068] According to some aspects, disclosed herein is an anode for a fluoride ion battery comprising a solid electrolyte interphase layer on an alkaline earth metal or rare earth metal anode. It should be understood that the anode metal or material may comprise an alloy or other suitable material. Figure 1B Examples of various anode metals and materials are shown. According to some aspects of the present disclosure, the anode disclosed herein comprises an outer layer of a solid electrolyte interphase (SEI) that provides a negative potential for extending the electrolyte or / and prevents the anode metal from dissolving to achieve reversibility of the anode while enabling the transfer of F- from the electrolyte to the anode ( Figure 3 ). Suitable compounds and methods for SEI formation are disclosed herein.

[0069] According to some aspects, the outer SEI layer is covalently bonded to the anode metal. Non-limiting examples of SEI bonding are shown in Figure 4 and Figure 5 The outer solid electrolyte interphase layer may include CF3(CF2)5CH2, CF3(CF2)2CH2, p-tert-butylphenyl, p-methoxyphenyl, p-(dimethylamino)phenyl, p-nitrophenyl, p-trifluoromethylphenyl, or a combination thereof. In some embodiments, Figure 5 As shown, the outer solid electrolyte interphase layer comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene ( Figure 4 ), 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof. In some embodiments, the outer solid electrolyte interphase layer can be a film on the anode, and can include 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof, and further includes a salt counter anion (including BF4(-)).

[0070] According to some aspects, methods of solid electrolyte interphase formation are disclosed herein. A method of making an anode having an SEI layer suitable for a fluoride ion battery may include coating a working electrode by the following steps: providing a liquid electrolyte comprising an additive; providing a working electrode in contact with the electrolyte, the working electrode comprising an alkaline earth metal, a rare earth metal, or a combination thereof; providing a counter electrode in contact with the electrolyte; and varying the voltage potential between the working electrode and the counter electrode between a first potential and a second potential for a plurality of cycles until the additive forms an outer solid electrolyte interphase layer on the working electrode, the second potential being higher than the first potential. In some embodiments, the working electrode may comprise calcium, cerium, lanthanum, or a combination thereof.

[0071] In some embodiments, relative to Li + / Li, the first potential can be about -0.8V and the second potential can be about +0.7V, the potential range can vary depending on the working electrode and additives used, the number of cycles can be up to 5 times, and the additive can include 1H,1H,2H,2H-perfluorooctyltriethoxysilane (FOTS); 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene (FH) or a combination thereof.

[0072] In some embodiments, relative to Li + / Li, the first potential can be about -1.0V and the second potential can be about +0.8V, the potential range can vary depending on the working electrode and additives used, the number of cycles can be up to 20 times, and the additive can include 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof.

[0073] The anodes and SEI layers disclosed herein can improve the electrical potential. Fig. 9A and Fig. 9B Depicted is an exemplary improvement in the negative potential of an additive-grafted calcium anode in a BTFE-based electrolyte determined by CV analysis: ( Fig. 9A )FH-grafted calcium anode in NpMe3NF-BTFE electrolyte; and ( Fig. 9B )FOTS-grafted calcium anode in Et3MeN.BF4-BTFE electrolyte.

[0074] According to some aspects, the present disclosure relates to a dedicated anode for a fluoride ion battery, comprising a metal (e.g., Ce, La, and Ca) as an active anode material and a solid electrolyte interphase (SEI) layer on the surface of the anode. In some embodiments, the SEI layer may comprise a fluorinated compound. According to some aspects, such as Figure 6As shown, the layer on the anode surface can have various properties depending on the properties of the compounds within the layer. In some embodiments, the SEI layer can include compounds that are stable on the anode surface, for example, a covalent reaction ( Figure 5 ), the diazonium salt has the structure of formula I:

[0075]

[0076] wherein X can be, for example, -C(CH3)3, -OCH3, -NMe2, -NO2 or -CF3.

[0077] The formation of the solid electrolyte interphase (SEI) layer can enable fluoride ion batteries to have a durable anode. Fig. 10A , 10B and 10C depict exemplary XPS studies of FH SEI and FOTS SEI grafted on the surface of calcium anode: Fig. 10A The XPS spectrum of FH SEI grafted on calcium anode is shown; Fig. 10B The XPS spectrum of FOTS SEI grafted on calcium anode is shown; Fig. 10C The ratio between fluorine and calcium active surface materials (F / Ca) in the SEI layer of FH and FOTS is shown. In another example, Fig. 10D The fluorination / defluorination of a cerium (Ce) anode with a FOTS SEI layer is shown. Fig. 10E XRD patterns corresponding to pristine Ce, Ce anode with FOTS SEI layer after fluorination (charging), and fluorinated Ce anode after defluorination (discharging) are shown.

[0078] In various embodiments, an anode disclosed herein may be combined with a cathode disclosed herein and a liquid electrolyte.

[0079] The SEI layer can be formed by any method known in the art, and the examples provided herein are non-limiting. In some embodiments, a reaction mechanism comprising one or more free radicals can be used to provide the SEI layer. According to some aspects, vapor deposition of the SEI layer can be utilized.

[0080] Liquid electrolytes (containing fluoride ions in solution) in fluoride ion batteries offer faster kinetics and can provide charging at room temperature, but the high reactivity of fluoride ions can lead to short battery life (e.g., electrode dissolution). - ) in aqueous solution shows a rapid reaction of the fluoride ions with water to form hydrofluoric acid (HF) and a complex ion HF2 - ( Figure 7). The formation of HF is highly corrosive and extremely toxic. In addition, in electrochemical applications, HF2 - Much less active than F-, and in extreme cases, may even be inactive. - It is also undesirable because it will evolve H2 at potentials below the target cathode reaction, thereby limiting the useful voltage window in electrochemical applications and potentially causing failure of cells containing the electrolyte.

[0081] Use non-aqueous F - Electrolyte solutions can be dissolved with aqueous F - However, non-aqueous F - Solutions have proven difficult to prepare at high enough concentrations (e.g., greater than or equal to 0.05 M) to be useful. According to some aspects of the present disclosure, a liquid electrolyte suitable for a fluoride ion battery (FIB) may include a fluoride salt and a non-aqueous solvent, wherein the fluoride salt is at least partially present in a dissolved state. The fluoride salt may be a metal fluoride or a non-metal fluoride. The solvent may be an organic liquid or an ionic liquid or a mixture of the two. In some embodiments, an electrolyte suitable for a FIB may include a composite electrolyte containing a fluoride salt, a polymer and optionally an organic liquid, an ionic liquid, or a mixture of the two.

[0082] Metal fluoride electrolyte salts are generally insoluble in organic matter at concentrations > 0.05 M. Organic fluoride electrolyte salts (e.g., with tetraalkylammonium (R4N + ) cations) may have improved solubility; however, synthesizing these in a truly anhydrous form is not trivial, as F – To HF2 – The decomposition of is prone to occur by elimination processes at high temperatures. Neopentyl-substituted (Np or 2,2-dimethylpropyl)alkylammonium salts, due to the branched Np chain (to improve solubility) and the lack of β-hydrogen (to inhibit decomposition on drying), were tested in organic solvents for their application in fluoride ion batteries (e.g. solubility, durability). After preliminary screening, for example, up to 100 g batches of dry N,N,N-trimethyl-N-neopentylammonium fluoride (Np1F) and N,N-dimethyl-N,N-dimethylpentylammonium fluoride (Np2F) were synthesized using an HF-titration procedure, and both showed suitability for FIBs compared to tetramethylammonium fluoride (TMAF).

[0083] Various organic solvents provide different levels of electrolyte longevity. For example, BTFE (2,2,2-trifluoroethylsulfone, bis(2,2,2-trifluoroethyl)ether) was found to provide a suitable voltage window ( Figure 8 ) and electrolyte life.

[0084] According to some aspects of the present disclosure, the liquid electrolyte for the FIB may include bis(2-methoxyethyl)ether, bis(2,2,2-trifluoroethyl)ether, N,N,N-trimethyl-N-neopentylammonium fluoride, N,N-dimethyl-N,N-dineopentylammonium fluoride, propionitrile, or a combination thereof. Using a suitable electrolyte, more durable components for room temperature rechargeable FIBs are disclosed herein, for example, due to the high energy density and high reaction potential ( Figure 1A ).

[0085] In some embodiments, disclosed herein is a cathode structure for a fluoride ion battery. According to some aspects, the cathode transition metal or electrochemically active material, such as Figure 1B As shown, further comprising one or more shells or layers. The cathode transition metal may have some dimensions at the nanoscale to improve, for example, efficiency and charge transfer. In some embodiments, the cathode may comprise a core-shell structure having a transition metal core and one or more shells at least partially surrounding the transition metal core, the outermost layer of the shell being in contact with the liquid electrolyte. Non-limiting examples of suitable copper core particles are shown in Fig. 12B , which is a TEM image of synthesized copper nanoparticles. According to some aspects, the cathode core structure or core can have a selected shape. For example, the core can include nanoparticles (e.g., spherical nanoparticles), nanocubes, nanotubes, nanowires, frames, sheets, nanoporous sheets, films, foams, or combinations thereof. According to some aspects, the size of the core can be determined by electronic conductivity or F - In an illustrative example, 20 nm may be the F - The distance limit of ion penetration. If the electron or F - If the ion path is greater than this distance limit (20 nm in this example), the electronic conductivity and / or F - Thus, according to some aspects, the core can include at least one dimension that is less than or equal to approximately the distance limit. For example, the core can include spherical nanoparticles having a diameter that is less than or equal to approximately the distance limit, because such spherical nanoparticles will be electrons or F particles that are less than or equal to approximately the distance limit in all directions. - It should be understood that the core may have one or more dimensions greater than approximately the distance limit, as long as it has a path approximately the distance limit in at least one direction. For example, the core may include a sheet (e.g., Fig.21According to some aspects, the distance limit can be about 20nm, optionally about 30nm, optionally about 40nm, and optionally about 50nm. According to some aspects, the distance limit can be about 20 to 80nm, optionally about 30 to 70nm, and optionally about 40 to 60nm. According to some aspects, the distance limit corresponds at least in part to some aspects of, for example, the core material and its shell. In particular, a shell with relatively low ionic resistance will provide a longer distance limit, because F- ions can more easily cross the shell to reach the core. A shell comprising a small thickness (e.g., less than 1nm) can provide a longer distance limit, because F- ions can more easily cross the shell to reach the core.

[0086] Examples of core structures (or cathode core particles) useful according to the present disclosure include, but are not limited to, nanoparticles having a diameter less than or equal to about the distance limit ( Fig.16 ), a nanowire having at least one dimension less than or equal to about the distance limit ( Fig.21 ), nanotubes with a wall thickness less than or equal to about the distance limit ( Fig.31 ), a thin sheet (e.g., a triangle, rectangle, square, sheet, circle, or oval) having a thickness less than or equal to about the distance limit ( Fig.32 ), a film having a thickness less than or equal to about the distance limit, a foam having a cell wall thickness less than or equal to about the distance limit, a sheet having a thickness less than or equal to about the distance limit, a frame having a thickness less than or equal to about the distance limit ( Fig.33 ), grids with line thickness less than or equal to approximately the distance limit, and combinations thereof.

[0087] The electrochemically active cathode structure or core further comprises a shell that at least partially surrounds the core. For example, the shell can surround the core so that the shell covers at least about 50%, optionally at least about 60%, optionally at least about 70%, optionally at least about 80%, optionally at least about 90%, optionally at least about 95%, and optionally at least about 100% of the surface area of ​​the core. According to some aspects, the molecular coverage of the shell on the core can be about 1 to 100 nm. -2 , optionally about 6 to 60 nm -2 For example, if the size of the core increases, the molecular coverage can increase. In some embodiments, as will be disclosed herein, the shell can include self-healing or self-fixing, flexible properties.

[0088] In some embodiments, the shell at least partially surrounding the core comprises a thickness, wherein the thickness ratio between the thickness of the metal nanostructure (cathode) core (at the thinnest dimension) and the thickness of the shell layer is from about 10:1 to about 1:1, optionally from about 9:1 to about 2:1, optionally from about 8:1 to about 3:1, optionally from about 7:1 to about 4:1, and optionally from about 6:1 to about 5:1.

[0089] According to some aspects, the thickness of the shell that at least partially surrounds the core is about 1nm to 1μm, optionally not more than 500nm, optionally not more than 200nm, optionally not more than 100nm, optionally not more than 50nm, not more than 10nm, optionally about not more than 9nm, optionally about not more than 8nm, optionally about not more than 7nm, optionally about not more than 6nm, optionally about not more than 5nm, optionally about not more than 4nm, optionally about not more than 3nm, optionally about not more than 2nm, and optionally about not more than 1nm. Further, all ranges can be optionally described as about 1-500nm, 1-200nm, 1-100nm, 1-50nm, 1-10nm, 1-5nm and 1-2nm.

[0090] According to some aspects, the shell may comprise a shell material that is compatible with a liquid F-shuttle battery or a fluoride ion battery. For example, the shell material may be selected so that dissolution of the cathode core material in the liquid electrolyte of the liquid F-shuttle battery during charging and / or discharging may be reduced or eliminated. The shell material may be selected to further provide sufficient charging time. As used herein, the term "charging time" refers to the length of time required for a discharged liquid F-shuttle battery electrode to be fully charged, i.e., the F in the fluoride conductive electrolyte. - The length of time required to travel from the anode to the cathode during charging of the battery. According to some aspects, the charging time can be between about 1 and 20 minutes, optionally about 1 to 10 minutes, and optionally about 3 to 5 minutes. However, the charging time is not limited and can depend on temperature and battery capacity, for example.

[0091] According to some aspects, disclosed herein is a method for manufacturing a cathode for a fluoride ion battery, an exemplary method comprising providing a solid transition metal and treating the solid transition metal with lanthanum and fluorine to form a LaF3 shell that at least partially surrounds the solid transition metal. As a non-limiting example, the solid transition metal may comprise bismuth, lead, copper, or a combination thereof. The treatment may comprise dispersing the solid transition metal in an aqueous solution of hydrazine hydrate and contacting the solid transition metal with an aqueous solution of lanthanum ions and fluoride ions. The aqueous solution of lanthanum ions and fluoride ions may comprise lanthanum nitrate hexahydrate and sodium fluoride. In some embodiments, the treatment may comprise radio frequency sputtering LaF3 onto a solid transition metal. In some embodiments, the transition metal cathode core may comprise a transition metal and the shell may comprise LaF3.

[0092] According to some aspects, the shell material may comprise a "soft shell" material. As used herein, "soft" refers to a material as described herein, particularly a material comprising at least one material capable of self-assembly as described herein. Examples of soft shell materials include, but are not limited to, surfactants, certain polymers, non-surfactant molecules having one or more specific functional groups, and combinations thereof. According to some aspects, the shell material may comprise an organic material, particularly an organic material comprising at least one material capable of self-assembly as described herein. Examples of organic shell materials include, but are not limited to, organic soft shell materials, such as organic surfactants, organic or organic molecule-containing polymers, non-surfactant organic molecules having one or more specific functional groups, and combinations thereof.

[0093] According to some aspects, the specific functional groups described herein can be selected from -COOH, -NH2, -COH, -OH, -SH, -PO3H, -SO3H, -CN, -NC, -R2P, -COO - 、-COO-OOCR、ethylene glycol、-C≡N、-N≡N + (BF4 - ), -Sac, -SR, -SSR, -CSSH, -S2O3 - Na + , -SeH, -SeSeR, -R2P=O, -PO3 2- / -P(O)(OH)2、-PO4 2- , -N≡C, -HC=CH2, -C≡CH, -SiH3, -SiCl3, -OCH2CH3, formula (I), formula (II), formula (III) and combinations thereof, wherein formula (I) is:

[0094]

[0095] Formula (II) is:

[0096]

[0097] And formula (III) is:

[0098]

[0099] wherein R' and R" are each independently an organic chain, in particular an organic chain capable of being partially or fully fluorinated, or an aryl group, alone or in combination with another R' or R", in particular an aryl group substituted with one or more fluorophilic groups. Exemplary organic chains useful for R' and R" include, but are not limited to -(CF2) n CF3, (CH2CF2) n CF3 and (CF2CH2O) n CF3. An example of a functional group according to formula (III) having at least one aromatic group is shown below as formula (IV):

[0100]

[0101] And formula (V):

[0102]

[0103]

[0104] It should be understood that each R' and R" can be the same as or different from another R' or R". According to some aspects, each R' can exhibit acceptable fluorination characteristics and / or each R" can exhibit acceptable stabilization characteristics. It should be further understood that, as described herein, the carbon atoms with non-shared valence electrons in the carbenes shown in formula (III) can be configured for connection with one or more molecules contained by the core.

[0105] According to some aspects, the surfactant may include a surfactant that can be used to prepare a core as described herein, such as a surfactant having one or more functional groups selected from a polar head (e.g., a polar head comprising one or more specific functional groups as described herein), a carbon-containing tail (e.g., an alkane, an alkyne, an alkene, and an aromatic ring), a fluorocarbon-containing tail (e.g., an aliphatic chain (e.g., (CF2) n , (CHF) n 、(CH2CF2) n and (CH2OCH2CF2) n ), and / or aryl (e.g. (C 6-x F x -) n)) and combinations thereof. Examples of surfactants useful according to the present disclosure may include, but are not limited to, oleylamine, oleic acid, tris(trimethylsilyl)silane, 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecanethiol, 2-(trifluoromethoxy)-benzenethiol, P-[12-(2,3,4,5,6-pentafluorophenoxy)dodecyl]-phosphonic acid, P-(3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl)-phosphonic acid, pentafluorobenzylphosphonic acid, perfluorododecanoic acid and combinations thereof.

[0106] According to some aspects, the certain polymers may include polymers that can be formed by in situ polymerization, particularly polymers that can be formed by in situ polymerization from their monomers or shorter oligomeric species. Additionally or alternatively, the certain polymers may be capable of self-healing by hydrogen bonding. For example, the certain polymers may be capable of hydrogen bonding, thereby autonomously and repeatedly "self-healing" defects in the shell, such as cracks and / or gaps, which may be caused at least in part by the volume expansion and / or contraction of the core during charge and discharge, as shown in Table 1 (below) and Fig.38 Examples of such polymers include, but are not limited to, polyvinylpyrrolidone (PVP), poly(methyl methacrylate) (PMMA), amino terminated and cross-linked polymers containing C=O bonds.

[0107] According to some aspects, the shell may comprise one or more monolayers. According to some aspects, the shell may comprise one, two, three or more monolayers. According to some aspects, each of the monolayers may be the same or different.

[0108] According to some aspects of the present disclosure, the shell material may include an inorganic material, such as a metal salt. Examples of the metal salt used to form the shell include alkali metal salts, alkaline earth metal salts, group 3 elements, group 13 elements, lanthanides, actinides, and transition metal salts. As used herein, "group 3 elements" refer to scandium (Sc), yttrium (Y), and groups of lanthanides and actinides. As used herein, "group 13 elements" refer to groups of boron (B), aluminum (Al), gallium (Ga), indium (In), and thallium (Tl). In certain embodiments, the metal salt used to form the shell includes lanthanum salts, cerium salts, and magnesium salts. In certain embodiments, the metal salt used to form the shell is selected from lanthanum salts and cerium salts. In certain embodiments, the metal salt is a lanthanum salt. In a preferred embodiment, the lanthanum salt is lanthanum nitrate. In some embodiments, the halide salt is sodium fluoride. In a non-limiting example, the shell comprises a material containing a metal fluoride or metal oxyfluoride (i.e., CeF3, CeOF, LaOF, LaF3). In some embodiments, the shell of the core-shell nanoparticle can be formed by mixing the separated metal nanoparticles used to form the core with, for example, a metal salt solution and a halide salt solution, which react to form a metal halide shell on the core. In some preferred embodiments, the metal salt solution may comprise barium nitrate and lanthanum nitrate in a ratio of about 1:10.

[0109] In some embodiments, core-shell nanoparticles may be provided that include a metal core surrounded by a metal halide or metal oxyhalide shell. A halide shell is provided that is tailored to protect the metal core nanoparticle from the electrode environment while maintaining the desired properties of the metal nanoparticle. In a non-limiting example, the core may include copper metal and the shell may include LaF3. In another non-limiting example, the core may include copper metal and the shell may include Ba x La 1-x F 3-x In some embodiments, X may be between about 0 and 0.5, optionally X may be 0.03.

[0110] Protective coatings useful for cathode structures include fluoride ion conducting phases that are chemically and electrochemically stable in the presence of a liquid FIB electrolyte. Such phases allow for F- exchange between the electrolyte and the active material. These include, for example, crystalline phases (e.g., LaF3, CaF2, SnF2, PbF2, PbSnF4), similar doped and / or solid solution phases (e.g., La 0.9 Ba 0.1 F 2.9 , Ca 0.8 Y 0.2 F 2.2 , Ca0.5 Ba 0.5 F2 and Pb 0.75 Bi 0.25 F 2.25 ), glass phases (e.g. 35InF3·30SnF2·35PbF2), and mixed fluoride / other anion phases (e.g. LaOF). Any material or phase that allows F-exchange between the electrolyte and the active material and has a bulk ionic conductivity greater than 10-10 S / cm at 298K is within the scope of the present disclosure. These phases are selected by considering the standard redox potential of the shell components and the internal species available in the standard background, and the components of these phases are selected to be electrochemically stable at the potential required for the reaction of the species contained in the coating.

[0111] Alternative protective coatings include polymers that are conductive to fluoride ions, such as borate-functionalized polymers, alkylammonium-functionalized polymers, or those featuring suitable functional groups.

[0112] The thickness of the protective coating is selected so that the F-exchange between the electrolyte and the active material occurs over a time course such that the charge / discharge of the electrochemical cell can be achieved at a suitable operating rate (e.g., C rate, corresponding to a complete charge or discharge of the energy stored in the electrochemical cell in one hour) at about 298K, and the charge / discharge of the electrochemical cell depends on the ionic conductivity of the coating material or phase. For example, LaF3 or Ba x La 1-x F 3-x The coating is most advantageously between 1-200 nm thick, such as between about 5 nm and about 20 nm thick, or any integer or sub-range therein. More generally, the coating thickness may be between about 1 nm and about 1 μm.

[0113] The electrode coatings disclosed herein may be formed by any suitable method. These may include solution chemistry techniques (e.g., forming the coating by precipitating a solid from a solution containing the fluoride or its component precursors), sol-gel or other soft chemistry or "chimie douce" methods, hydrothermal synthesis, vacuum methods (e.g., chemical vapor deposition), physical vapor deposition, sputtering, laser ablation and molecular beam epitaxy, electrochemical deposition, or post-deposition material fluorination by reaction with a fluorine source. For example, a preferred method for preparing a LaF3 coating is a sol-gel synthesis. As desired, the prepared coating may optionally be subjected to high temperatures in air or an inert gas (e.g., Ar) for an annealing step. For example, a LaF3 coating prepared by a sol-gel method may be heated to 500°C in air to anneal the coating and help remove impurities (e.g., solvents). In this way, a fluoride-conducting coating phase may be synthesized as desired by adjusting the precursor materials, their stoichiometric ratios, and the initial reaction post-annealing step. This sol-gel synthesis of the LaF3 coating may also be modified to prepare BaF3. x La 1-x F 3-x In some embodiments, a La2O3 coating can be made using a sol-gel method, followed by post-fluorination using F2 or HF to convert a large portion of the oxide into LaOF and / or LaF3.

[0114] In another example, the LaF3 coating can be obtained from precipitation by slowly adding NH4F to an aqueous La(NO3)3 solution in which nanoparticles of the core material are suspended. Since LaF3 is very poorly soluble in water, its crystallization will start on the surface of the suspended nanoparticles. The precipitation synthesis of the LaF3 coating can also be modified to prepare Ba x La 1- x F 3-x coating.

[0115] Fluoride-conductive encapsulants and / or coating phases and materials can be prepared on three-dimensional structures (e.g., metal or metal fluoride nanoparticles, or aggregates of nanoparticles), two-dimensional structures (e.g., metal or metal fluoride films), or one-dimensional structures (e.g., fibers or tubes of metal or metal fluoride) as desired. Similarly, fluoride-conductive phases can be prepared on the outer and / or inner surfaces of complex microporous or mesoporous structures (e.g., zeolites or highly ordered template materials). This can include, but is not limited to, mesoporous silica (e.g., MCM-41 or SBA-15) or metal-organic frameworks or similar coordination polymers.

[0116] A non-limiting example of a method for preparing suitable core-shell nanoparticles can include providing a first mixture comprising metal nanoparticles and a reducing agent, and mixing the first mixture with a solution comprising one or more metal salts and halide salts to form a metal halide or oxyhalide shell on the metal nanoparticles. In a non-limiting example, the solution comprises a metal salt and a halide salt. In another non-limiting example, the solution comprises two metal salts and a halide salt. In some such examples, one of the two metal salts is a barium salt. In other such examples, the two metal salts comprise a barium salt and a lanthanum salt. Another exemplary method for preparing core-shell nanoparticles or nanostructures can include sputtering. In some embodiments, the sputtering can include LaF3 or Ba x La 1-x F 3-x RF sputtering onto solid transition metals.

[0117] In some examples, the synthesis of core materials is disclosed herein. In general, metal nanoparticles used as cathode metal cores can be synthesized by reacting a metal salt solution with a reducing agent in the presence of one or more stabilizers. In an illustrative example, the metal salt solution contains copper (II) nitrate hemipentahydrate (Cu(NO3)2.2.5H2O) as the metal salt. The metal salt is mixed with CTAB (hexadecyltrimethylammonium bromide) and water, and the pH of the mixture can be adjusted to a pH of about 10-11 with, for example, ammonium or sodium hydroxide.

[0118] Before the reducing agent is added to the metal salt solution, the reducing agent can be mixed with one or more stabilizers and water, and mixed for a period of time, such as about twenty minutes, and then combined with the metal salt solution. The reducing agent is selected from hydrazine, sodium borohydride, sodium cyanoborohydride, sodium dithionite, sodium dithionite, iron (II) sulfate, tin (II) chloride, potassium iodide, oxalic acid, formic acid, ascorbic acid, thiosulfate, dithionite, phosphorous acid, phosphite and hypophosphite. In a preferred embodiment, the reducing agent is hydrazine.

[0119] The metal salt solution and the reducing agent are combined to form the metal nanoparticles. The synthesis of the metal nanoparticles is carried out in an oxygen-free atmosphere. Illustrative examples of oxygen-free atmospheres include, but are not limited to, nitrogen, argon, helium, hydrogen, and mixtures thereof. After synthesis, the metal nanoparticles are separated from the synthesis solution. It should be understood that the method for separating the metal nanoparticles is not limited and may include one or more techniques, such as filtering, decantation, and centrifugation. The metal nanoparticles may be washed with a solvent (e.g., ethanol) one or more times to remove any residual stabilizer or other organic material from its surface.

[0120] Typically, the separated metal nanoparticles can be redispersed in an aqueous solution containing an additional reducing agent under an oxygen-free atmosphere. Then the mixture containing the separated metal nanoparticles and the reducing agent is mixed with a metal salt solution and a halide salt solution for forming the metal halide shell on the metal nanoparticle core under an oxygen-free atmosphere. The metal salt solution and the fluoride salt solution for forming the shell can be added to the nanoparticle mixture in sequence, or the metal salt solution and the fluoride salt solution for forming the shell can be added to the nanoparticle mixture at the same time. In some embodiments, the metal salt solution comprises a single metal salt. In other aspects, the metal salt solution comprises two metal salts. In some such aspects, the metal salt solution comprises a barium salt. In some such aspects, the metal salt solution comprises a barium salt and a lanthanum salt. In some such aspects, the metal salt solution comprises barium nitrate and lanthanum nitrate. In some such aspects, the metal salt solution comprises barium nitrate and lanthanum nitrate in a ratio of about 1:10.

[0121] According to some aspects, useful structures and compositions include those that encapsulate a metal or metal fluoride within a fluoride ion conductive coating such that sufficient void space exists within the encapsulation to accommodate volume changes between the metal and metal fluoride phases (or between a lower valent metal fluoride species MFm and a higher valent metal fluoride species MFn, where n>m for the same metal M) upon conversion without rupture of the coating phase or material. Such structures and compositions are sized to fit within a fluoride-conducting encapsulant, and in some cases, there is at least sufficient void space available to convert up to 100% of the encapsulated metal atoms to the appropriate metal fluoride phase (e.g., for the process of Fe→FeF3, at least 211% void space is required compared to the starting volume of Fe (from Table 1 below). In other cases, the extent of conversion can be controlled electrochemically (e.g., by controlling voltage limits and / or charge / discharge capacity) so that the encapsulant does not rupture during cycling if there is insufficient void space to achieve 100% conversion. In addition, structures and compositions are also contemplated in which the fluoride-conducting encapsulant is conformal or its void space is insufficient to fully accommodate the conversion from metal to metal fluoride, but has suitable flexibility to stretch or shrink without breaking or cracking the encapsulant. Such compositions can be two-dimensional (e.g., membrane-void-coating), or three-dimensional (e.g., nanoparticle-void-coating), or more complex configurations (e.g., metal-impregnated zeolite-void-coating) as desired.

[0122] In some embodiments, a plurality of concentrically arranged encapsulants are disclosed herein. Each concentrically arranged encapsulant may be separated by a gap and may be composed of the same or different materials. Also in other embodiments of concentrically arranged encapsulants, the active material and the outermost encapsulant (in contact with the electrolyte) may be separated by a polymer or other flexible material that allows fluoride ions to pass through and can adapt to the volume change during the cycle in size without the rupture of the outermost encapsulant, as shown in Table 1.

[0123] Table 1: Volume changes for metal to metal fluoride conversion

[0124]

[0125]

[0126] The coating encapsulating the FIB electrode material particles disclosed herein covers such significant volume changes, and due to the volume changes, one particular charge state is not necessarily conformal to particles in a different charge state. Compositions and methods are disclosed herein that protect the electrode active material from side reactions with the electrolyte, allow ion conduction through the encapsulant, and have sufficient void space within the encapsulant and / or have sufficient encapsulant expansion / contraction properties to accommodate the volume changes of the active material during charge and discharge without allowing direct contact between the active material and the electrolyte. In some embodiments, depending on the composition of the electrode active material, sufficient void space can be no void space.

[0127] As will be appreciated, an active material that is completely surrounded and located within an encapsulant but has at least some remaining void space and / or compressible inactive material (e.g., polymer) can be referred to as a "yolk-shell" nanocomposite structure. Such a fully encapsulated structure can be based on various compositional arrangements of active materials and fluoride-conducting encapsulants. However, other arrangements including active materials that are only partially surrounded by a fluoride-conducting protective layer are also contemplated. Such a structure can include a two-dimensional or three-dimensional non-fluoride-conducting support structure (e.g., a membrane, a side-opening chamber, a tube, etc.) containing the active material, one or more sides of which are coated with a fluoride-conducting material to allow ion transport. Such a support structure can contain void space or a dimensionally flexible polymer or other material to accommodate volume changes during cycling without damaging the support structure or the encapsulant.

[0128] Suitable preparation strategies for "yolk-shell" nanocomposites that can be used in FIB electrochemical cells are described herein. In certain embodiments, Cu metal or CuF2 will be used as examples of active material "yolk", and LaF3 will be used as examples of encapsulant or "shell" materials. As previously stated, these are not limiting of the invention, as any material that can accommodate or release fluoride ions after an electrochemical reaction can be envisioned to constitute the "yolk", and any phase or material that allows F-exchange between the electrolyte and the active material can be envisioned to constitute the encapsulant or shell. In certain embodiments, the diameter of the active material is less than 1 μm, and most advantageously, the diameter of the active material "yolk" is between 1 and 500 nm, and the thickness of the encapsulant is 2 to 100 nm.

[0129] Fig.39 A general route using a sacrificial inorganic "intermediate" layer such as SiO2 is depicted. For example, Cu can be reduced using hydrazine or a similar reducing agent in the presence of a stabilizing and / or coordinating substance such as sodium citrate and / or a surfactant such as hexadecyltrimethylammonium bromide. 2+ The copper nanoparticles are prepared by exposing the copper nanoparticles to a surface-modifying ligand, such as aminopropyltrimethoxysilane, APTS (or other suitable bifunctional substances, so that one part of the molecule coordinates with the copper surface and the other part presents a reactive silicon part to the external environment), and then under appropriate conditions (e.g. The addition of a hydrolyzable silica source, such as tetraethoxyorthosilicate (TEOS) or sodium silicate solution (water glass), during a reaction (synthesis or sol-gel reaction) results in a conformal coating of the Cu nanoparticles with SiO2. The thickness of the SiO2 layer (and the resulting void space) can be controlled by varying the amount of SiO2 precursor used and the reaction conditions. The SiO2-coated Cu nanoparticles are then coated with an outer LaF3 layer by a sol-gel reaction (optionally in the presence of a surfactant (e.g., Lutensol AO)), whereby the thickness of the coating can be varied by the amount of LaF3 precursor used and the reaction conditions. This step can be performed after the intermediate Cu@SiO2 material is isolated and / or purified, or can be performed in the same reaction mixture after the SiO2 layer is formed. The resulting Cu@SiO2@LaF3 composite can optionally be subjected to an annealing step, and / or the SiO2 layer can then be removed by exposing the composite to a SiO2 etchant material (e.g., NaOH or HF) under appropriate conditions to obtain a Cu@LaF3 "yolk-shell" composition. The material may then optionally be subjected to a final annealing step in the presence of a reducing agent (eg H2) to purify the Cu surface.

[0130] Fig.40A similar route using a sacrificial polymer "intermediate" layer is depicted. For example, copper nanoparticles are coordinated by a polymer shell; by forming the copper nanoparticles in the presence of a polymer or copolymer featuring amino, hydroxyl, carboxylic acid or other ionizable functional groups (e.g., poly(acrylic acid), poly(ethyleneimine), polyvinyl alcohol, polystyrene sulfonate), protein, polysaccharide, or gelatin; or by growing a polymer from the surface of an appropriately modified copper nanoparticle (e.g., poly(styrene sulfonate) grown by atom transfer radical polymerization from an 11-aminoundecyl 2-bromoisobutyrate functionalized surface). The thickness of the polymer layer (and the resulting void space) can be controlled by polymer concentration and / or molecular weight. A shell of LaF3 is grown around the exterior of the Cu@polymer nanocomposite by a sol-gel reaction to provide a Cu@polymer@LaF3 nanocomposite. The polymer layer is then removed by decomposition at elevated temperature (in air or under an inert gas (e.g., Ar)) or dissolution in a suitable solvent (e.g., toluene, dichloromethane, or acetone) to yield the desired Cu@LaF3 "yolk-shell" composition. The material can then optionally be subjected to a final annealing step in the presence of a reducing agent (e.g., H2) to purify the Cu surface. Alternatively, a polymer core-shell structure (e.g., hollow latex-type particles) can be used as a template in which Cu nanoparticles are entrapped (by exposing Cu nanoparticles to preformed hollow latex particles or by coordinating Cu ions in solution with ionizable prepolymers or copolymers, followed by reduction of the copper ions to give copper nanoparticles, followed by, for example, solvent removal to generate the hollow structure), followed by growth of the LaF3 shell, removal of the polymer, and annealing (as desired) to generate the Cu@LaF3 "yolk-shell" composition.

[0131] Fig.41 An alternative route is depicted in the absence of a sacrificial "intermediate" layer. For example, Cu nanoparticles are treated with a suitable surface-modifying ligand (e.g., 11-aminoundecanoic acid, AUDA), followed by the growth of an outer LaF3 layer by a sol-gel reaction to produce a Cu@LaF3 "core-shell" complex, which can then optionally be followed by an annealing step. Partial etching of the Cu "core" using an appropriate etchant (e.g., KCN, HCl / H2O2, or FeCl3; suitable etchants are known in the art, and suitable etchants can be selected so as not to affect the "shell" material) through control of reaction conditions (e.g., etchant concentration, temperature, reaction time) creates void spaces in the Cu@LaF3 particles, thereby providing a "yolk-shell" Cu@LaF3 composition. This material can then optionally be subjected to a final annealing step in the presence of a reducing agent (e.g., H2) to purify the Cu surface.

[0132] Fig.42A variation of the above-described "sacrificial" synthesis is depicted in which nanoparticles of the active material are grown on the surface of a "sacrificial" material (here, the innermost material that is removed). For example, one or more Cu nanoparticles are grown on the surface of amino-functionalized poly(styrene) or SiO2 particles. The resulting composite is treated with a suitable Cu surface-modifying ligand and then the outer layer of LaF3 is grown by a sol-gel reaction. The innermost material is removed by thermal decomposition, etching, or dissolution to form a "yolk-shell" Cu@LaF3 composition characterized by one or more Cu nanoparticles. The material can then optionally be subjected to a final annealing step in the presence of a reducing agent (e.g., H2) to purify the Cu surface and optionally aggregate the Cu nanoparticles.

[0133] Fig.43 An alternative strategy is depicted in which the active material grows within the internal structure or pores of a preformed "sacrificial" material. For example, Cu nanoparticles can be grown inside hollow SiO2 nanospheres. These Cu@SiO2 "core-shell" nanocomposites are then coated with an outer layer of LaF3 by a sol-gel reaction (optionally in the presence of a surfactant (e.g., Lutensol AO)), whereby the thickness of the coating can be varied by the amount of LaF3 precursor used and the reaction conditions. The resulting Cu@SiO2@LaF3 composite can optionally be subjected to an annealing step, and / or the SiO2 layer can then be removed by exposing the composite to a SiO2 etchant material (e.g., NaOH or HF) under appropriate conditions to obtain a Cu@LaF3 "yolk-shell" composition. The material can then optionally be subjected to a final annealing step in the presence of a reducing agent (e.g., H2) to purify the Cu surface. In a related synthesis, microporous or mesoporous materials (e.g., zeolites) can be used as "templates" for the formation of Cu nanoparticles, and Cu@LaF3 "yolk-shells" can then be generated in a similar manner.

[0134] Fig.44 A similar alternative strategy has also been described, in which a highly electropositive metal or its metal fluoride (e.g., CaF2) is grown in the interior space of a hollow material (e.g., poly(styrene)-poly(acrylic acid) latex copolymer) in a suitable solvent. These polymer-encapsulated CaF2 nanocrystals are then coated with an outer layer of a fluoride ion conducting material of suitable electrochemical stability to allow them to be electrochemically stable at the conversion potential of CaF2 to Ca (~0.2 V vs. Li + / Li) itself is not reduced. Examples of suitable protective materials include solid solutions such as Ca x Ba y F2(x+y=1), wherein the Ca in the protective shell 2+ and Ba 2+The ions are not substantially reduced during the conversion reaction of the CaF2 particles within the shell; instead, the shell itself, which features a low electropositive metal element (e.g., LaF3), will be reduced preferentially over the inner CaF2 particles. x Ba y The F2 composite can optionally be subjected to an annealing step, and / or the polymer layer can then be removed by exposing the composite to an elevated temperature or a suitable solvent etchant material that removes the polymer to obtain the CaF2@Ca x Ba y F2 "yolk-shell" composition.

[0135] Using the described encapsulated active materials and / or yolk-shell nanocomposite electrodes, as well as electrolytes, anodes with SEI, binders, additives, separators, battery housings or packaging, current collectors, electrical contacts, electronic charge and discharge controllers and other elements of battery construction known to those skilled in the art, useful fluoride ion batteries can be made that can operate in a temperature range of -40 degrees Celsius to 200 degrees Celsius. Such electrochemical cells can have substantially irreversible electrochemical reactions during discharge, making them suitable for use in forming galvanic cells or primary cells. Alternatively, certain structures and compositions having electrochemical reactions that are at least partially reversible by the application of an electrical charge can form secondary (storage) batteries.

[0136] exist Figure 1C In some embodiments shown, the core-shell nanoparticles comprise a core comprising a metal or metal alloy ("Me"), and a shell comprising a metal halide or metal oxyhalide. The metal of the core can be the same as the metal of the metal halide shell. In some embodiments, the metal of the core and the metal of the metal halide or metal oxyhalide shell are different metals. In some embodiments, the metal halide shell itself can comprise two metals. The core-shell nanoparticles of the present disclosure can be incorporated into a variety of methods and applications, including but not limited to use in electrochemical cells (including Figure 2 The energy density of various types of batteries is shown in Figure 1A And in Table 2 below:

[0137] Table 2. Energy density of F-shuttle cells and lithium-ion batteries

[0138]

[0139]

[0140] In some embodiments, the metal nanoparticles used to form the core can be synthesized in the presence of a stabilizer that prevents or inhibits oxidation of the metal nanoparticles during synthesis and can be easily removed from the metal nanoparticles before the metal halide or metal oxyhalide shell is formed thereon. For example, bulky polymers such as polyvinyl pyrrolidone (molecular weight of 55,000 g / mol) used during the synthesis of metal nanoparticles inhibit oxidation of metal nanoparticles. However, these stabilizers are not easily removed from the metal nanoparticles after synthesis. Without being limited by any particular theory, residual stabilizers can form additional layers between the core formed by the metal nanoparticles and the metal halide or oxyhalide shell, which reduces the performance of the core-shell nanoparticles in the desired system. For example, it is desirable to maintain the conductivity of core-shell nanoparticles used as electrode materials in F shuttle cells. However, core-shell materials containing additional layers of residual stabilizers between the core and the shell may result in increased space between electrode materials; the additional layers of residual stabilizers and / or the resulting increased space may reduce the conductivity of the core-shell material. Without wishing to be bound by any particular theory, the additional layer of the stabilizer may hinder the contact between the core and the shell to conduct fluoride ions, while the absence of the stabilizer may increase the likelihood of fluoride ions from the core being conducted to the shell.

[0141] Therefore, the stabilizer can be used in the synthesis of the metal nanoparticles for forming the core, and the stabilizer is easy to remove therefrom to minimize the amount of the stabilizer on the surface of the core, and then the metal halide or metal halide shell is formed directly thereon. In a non-limiting example, the molecular weight (individual or weight average) of the one or more stabilizers that can be used in the synthesis of the metal nanoparticles is less than 1000 g / mol, optionally less than 500 g / mol, optionally less than 375 g / mol, and optionally less than 350 g / mol. Illustrative examples include hexadecyl trimethyl ammonium bromide (CTAB) with a molecular weight of 364 g / mol, citric acid with a molecular weight of 192 g / mol, and mixtures thereof.

[0142] In a non-limiting example, the shell is deposited directly on the metal core and can be Figure 1CThe core is completely surrounded by the core. In some embodiments, the shell of the core-shell nanoparticle can be formed by mixing the separated metal nanoparticles for forming the core with, for example, a metal salt solution and a halide salt solution, and the metal salt solution and the halide salt solution react to form the metal halide shell on the core. In some embodiments, the metal salt for forming the shell is selected from alkali metal salts, alkaline earth metal salts and transition metal salts. In certain embodiments, the metal salt for forming the shell is a transition metal salt. In certain embodiments, the metal salt for forming the shell is selected from lanthanum salts, cerium salts and magnesium salts. In certain embodiments, the metal salt for forming the shell is selected from lanthanum salts and cerium salts. In certain embodiments, the metal salt is a lanthanum salt. In a preferred embodiment, the lanthanum salt is lanthanum nitrate. In some embodiments, the halide salt is sodium fluoride. In a non-limiting example, the shell comprises a material containing metal fluoride or metal fluoride oxide (i.e., CeF3, CeOF, LaOF, LaF3). In some embodiments, the metal salt solution may include barium nitrate and lanthanum nitrate. In some embodiments, the metal salt solution comprises barium nitrate and lanthanum nitrate in a ratio of about 1:10.

[0143] In other embodiments, as described above, the core (or electrode active material) can be separated from the shell (or encapsulant) by void space. Compositions and methods according to such embodiments can protect the electrode active material from side reactions with the electrolyte, allow ion conduction through the encapsulant, and have sufficient void space within the encapsulant and / or have sufficient encapsulant expansion / contraction properties to accommodate the volume changes of the electrode during charge and discharge without allowing the active material and the electrolyte to be in direct contact.

[0144] The terms core and electrode active material are used interchangeably herein. Similarly, the terms shell, layer and encapsulating agent are used interchangeably herein.

[0145] In other embodiments, the present disclosure relates to an electrode comprising the core-shell nanoparticles disclosed herein. All aspects and embodiments described about the core-shell nanoparticles and methods for making the same are applicable to the electrode. In a non-limiting example, the electrode is part of a F shuttle or fluoride ion battery system.

[0146] In some embodiments, the present disclosure is directed to an electrochemically active structure comprising: a core comprising an active material; and a fluoride-containing shell at least partially surrounding the active material, wherein the fluoride-containing shell comprises a first metal and a second metal, and the first metal is barium.

[0147] In some embodiments, the active material (core) comprises copper nanoparticles. In some embodiments, the fluoride-containing shell core may be directly connected to the core. In some embodiments, the second metal is lanthanum. In some embodiments, the barium and the lanthanum are present in a ratio of x:1-x. In some embodiments, x is from about 0.03 to about 0.15. In some embodiments, x is about 0.03. In some embodiments, the present disclosure relates to an electrode comprising: a core comprising copper nanoparticles; and a fluoride-containing shell at least partially surrounding the copper nanoparticles, wherein the fluoride-containing shell comprises barium and lanthanum in a ratio of x:1-x. In some embodiments, x can be from about 0.03 to about 0.15.

[0148] In some embodiments, the present disclosure is directed to a method of preparing coated metal nanoparticles, the method comprising: a) providing a water / metal nanoparticle mixture; b) exposing the water / metal nanoparticle mixture to an inert atmosphere; and c) forming a fluoride-containing shell around a metal nanoparticle core, wherein the fluoride-containing shell comprises a first metal and a second metal, and the first metal is barium.

[0149] In some embodiments, forming the fluoride-containing shell comprises adding a first metal salt, a second metal salt, and a fluoride-containing salt to the water / metal nanoparticle mixture to form a fluoride-containing shell around the metal nanoparticle core, wherein the first metal is a barium salt. In some embodiments, the second metal is a lanthanum salt. In some embodiments, the first metal salt is barium nitrate and the second metal salt is lanthanum nitrate. In some embodiments, the barium nitrate and the lanthanum nitrate are used in a molar ratio of about 1:10.

[0150] The core-shell particles having a transition metal core and a shell at least partially surrounding the transition metal core can be applied to a metal cathode or can be supported in various ways for use in a fluoride ion battery. According to some aspects, an aggregate of a transition metal core and a shell at least partially surrounding the transition metal core is formed for use in a suitable cathode. In some embodiments, the suitable cathode has a larger dimension extending from the shell, while the shell encompasses nanometer dimensions.

[0151] According to some aspects, the core-shell particles with a transition metal core and a shell at least partially surrounding the transition metal core can be formed into a paste, can be combined with other compounds, can be dried, can be shaped, can be aggregated or can be used in any manner known in the art. In some embodiments, the core-shell particles with a transition metal core and a shell at least partially surrounding the transition metal core can be made into a paste with poly (vinylidene fluoride), PVDF and / or SP (Super P carbon black), pressed into a stainless steel grid, and dried under vacuum for electrode assembly.

[0152] "Inert atmosphere" refers to a gaseous mixture containing little or no oxygen and comprising one or more inert or non-reactive gases that have a high threshold before reacting. The inert atmosphere can be, but is not limited to, molecular nitrogen or an inert gas (such as argon) or a mixture thereof.

[0153] A "reducing agent" is a substance that causes another substance to be reduced when it itself is oxidized. Reduction refers to the gain of electrons by a chemical, while oxidation refers to the loss of electrons by a chemical.

[0154] A "metal salt" is an ionic complex in which one or more cations are one or more positively charged metal ions, and one or more anions are one or more negatively charged ions. "Cation" refers to a positively charged ion, and "anion" refers to a negatively charged ion. In a "metal salt" according to the present disclosure, the anion can be any negatively charged chemical species. The metal in the metal salt according to the present disclosure can include, but is not limited to, an alkali metal salt, an alkaline earth metal salt, a transition metal salt, an aluminum salt, or a post-transition metal salt and a hydrate thereof.

[0155] An "alkali metal salt" is a metal salt wherein the metal ion is an alkali metal ion, or a metal in Group 1 of the Periodic Table of the Elements (eg, lithium, sodium, potassium, rubidium, cesium, or francium).

[0156] An "alkaline earth metal salt" is a metal salt wherein the metal ion is an alkaline earth metal ion, or a metal in Group 2 of the Periodic Table of the Elements (eg, beryllium, magnesium, calcium, strontium, barium, or radium).

[0157] A "transition metal salt" is a metal salt in which the metal ion is a transition metal ion, or a metal in the d-block of the periodic table (including the lanthanides and actinides). Transition metal salts include, but are not limited to, salts of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, hafnium, tantalum, tungsten, rhenium, osmium, iridium, platinum, gold, mercury, actinium, thorium, protactinium, uranium, neptunium, plutonium, americium, curium, berkelium, californium, einsteinium, fermium, mendelevium, nobelium, and lawrencium.

[0158] A "late transition metal salt" is a metal salt wherein the metal ion is a late transition metal ion (eg, gallium, indium, tin, thallium, lead, bismuth, or polonium).

[0159] A "halide salt" is an ionic complex wherein the anion is a halide ion (including but not limited to fluoride, chloride, bromide, and iodide). A "fluoride salt" is an ionic complex wherein the anion is a fluoride ion. According to the present disclosure, the halide salt or the cation of the fluoride salt can be any positively charged chemical species.

[0160] "Metal fluoride" is an ionic complex in which the cation is one or more metal ions and the anion is a fluoride ion. According to some aspects of the present disclosure, the metal salt and the fluoride salt react to form a metal fluoride shell around the metal nanoparticle core. Similarly, "metal halide" is an ionic complex in which the cation is one or more metal ions and the anion is a halide ion.

[0161] A "fluoride-containing" salt is an ionic complex in which the anion comprises a fluoride ion but is not limited to a fluoride ion. In contrast, a "fluoride-containing" salt includes an ionic complex in which the anion comprises a fluoride complex itself with other ions or atoms. "Fluoride-containing" salts suitable for use in aspects of the present disclosure include those known to those of ordinary skill in the art, including but not limited to fluoride salts, non-metallic fluoride anions (e.g., tetrafluoroborate and hexafluorophosphate), and fluoride oxide salts. In some embodiments of the present disclosure, the fluoride-containing salt may include quaternary ammonium fluoride and a fluorinated organic compound. According to some aspects of the present disclosure, the metal salt and the fluoride-containing salt react to generate a fluoride-containing shell around the metal nanoparticle core.

[0162] The term "electrode" refers to an electrical conductor in which ions and electrons are exchanged with an electrolyte and an external circuit. In this specification, "positive electrode" and "cathode" are used synonymously and refer to an electrode with a higher electrode potential (i.e., higher than (xi) negative electrode) in an electrochemical cell. In this specification, "negative electrode" and "anode" are used synonymously and refer to an electrode with a lower electrode potential (i.e., lower than the positive electrode) in an electrochemical cell. Cathode reduction refers to the chemical substance gaining electrons, while anodic oxidation refers to the chemical substance losing electrons. The positive and negative electrodes of the present invention can be provided according to a series of useful configurations and form factors known in the field of electrochemistry and battery science (including thin electrode designs, such as thin film electrode configurations).

[0163] The term "electrochemical cell" refers to a device and / or device component that converts chemical energy into electrical energy or vice versa. An electrochemical cell has two or more electrodes (e.g., a positive electrode and a negative electrode) and an electrolyte, wherein electrode reactions occurring on the surfaces of the electrodes result in a charge transfer process. Electrochemical cells include, but are not limited to, primary cells, secondary cells, and electrolytic systems.

[0164] "Electrolyte" refers to an ionic conductor that may be a solid, liquid (most commonly), or more rarely a gas (eg, a plasma).

[0165] Example 1. Cu nanoparticles encapsulated in LaF3 and barium-doped LaF3 shells. Fig.13A Cu@LaF3 core-shell nanoparticles and Cu@La 0.97 Ba 0.03 F 2.97TEM image of core-shell nanoparticles. Fig.13A The central black region corresponds to the copper core, while the peripheral black and white regions correspond to LaF3 or La 0.97 Ba 0.03 F 2.97 shell. This figure shows the direct coating of LaF3 or La 0.97 Ba 0.03 F 2.97 Uniform coverage of the copper core by the shell.

[0166] Fig. 13B Schematic showing the formula Cu@La 0.97 Ba 0.03 F 2.97 Core-shell nanoparticles with shells; including Cu@LaF3 for comparison. Initially, the copper nanoparticle core can be up to about 50 nm in diameter before use, and LaF3 or La 0.97 Ba 0.03 F 2.97 The thickness of the coating can be about 5 nm. The CuF2 layer formed around the Cu core during battery charging can grow to a thickness of about 3 nm in Cu@LaF3 nanoparticles. However, by doping Ba into the LaF3 shell, the CuF2 layer can grow to a greater thickness, such as about 10 nm ( Fig. 13B middle).

[0167] Fig.14A and 14B The capacity improvement achieved after Ba doping is illustrated. Fig.14A The Cu@LaF3 electrode or Cu@La 0.97 Ba 0.03 F 2.97 Electrode compared to Ag / Ag + The voltage curve of the first charge-discharge cycle of the reference electrode. 0.97 Ba 0.03 F 2.97 ) has a capacity of 95.2 mAh / g, compared with only 50.2 mAh / g for Cu@LaF3 ( Fig. 14B). Therefore, Ba doping of the LaF3 shell almost doubles the cathode electrode capacity. By Ba doping, the ionic conductivity of the LaF3 shell is improved by about 100 times. Fluoride ions can more easily pass through the shell to react with Cu to form CuF2, and the amount of CuF2 formed directly determines the capacity of the battery. The more CuF2 is formed, the higher the capacity of the battery. Therefore, the utilization rate of Cu can be almost doubled by Ba doping of the LaF3 shell. Cu or CuF2 can be used as cathode materials for liquid-type F-shuttle batteries. These materials are relatively cheap and lightweight, which provides high capacity and high energy density. The theoretical capacity of CuF2 is 528mAh / g. However, pure Cu or CuF2 easily dissolves into the liquid electrolyte during charging and discharging. To solve this problem, the copper core is coated with LaF3 or Ba-doped LaF3 shell structure, which effectively prevents Cu from dissolving during charge / discharge cycles. As for Cu@LaF3, for example, the LaF3 shell effectively prevents Cu from dissolving during charge / discharge. As a result, Cu can be converted to CuF2 during charging, and CuF2 can be reduced to Cu during discharge. 0.97 Ba 0.03 F 2.97 ), the ionic conductivity of the shell can be increased by 100 times compared to the LaF3 shell, that is, the shell has a low resistance. - Ions can more easily pass through the shell, so that more Cu can be fluorinated to CuF2 during charging. Compared with the undoped LaF3 shell, the capacity is doubled (see Fig.14A and 14B as well as Fig.15 ).

[0168] Fig.45 Schematic showing the formula Cu@Ba x La 1-x F 3-x Core-shell nanoparticles with shells; Cu@LaF3 is included for comparison. Initially, the diameter of the copper nanoparticle core can be up to about 50 nm, and the LaF3 or Ba x La 1-x F 3-x The thickness of the coating can be about 5 nm. The CuF2 layer formed on the Cu core during battery charging can grow to a thickness of about 3 nm in Cu@LaF3 nanoparticles. However, by doping Ba into the LaF3 shell, the CuF2 layer can grow to a greater thickness.

[0169] Example 2. Design and Synthesis of Cu Nanostructures Since many metal fluorides have poor electronic and ionic conductivity, it is necessary to design the structure of the metal fluorides to fully utilize the active material and achieve its specific capacity and energy density.

[0170] In one embodiment, in order to better utilize the Cu / CuF2 electrode material to achieve an energy density close to its theoretical capacity (i.e., 843.5 mAh / g for Cu and 528 mAh / g for CuF2), it is preferred to tailor the structural design to meet the following requirements: the thickness of the Cu nanomaterial along at least one direction or axis of the Cu nanostructure is no more than 20 nm. In these structures, the copper can be in the range of 5-20 nm with LaF3 or La 1-x Ba x F 3-x Coating / covering of electrode active materials.

[0171] Examples of such Cu nanostructures include nanoparticles, nanotubes, nanowires, nanoframes, nanosheets, nanoporous, sheets and films. According to some aspects, such Cu nanostructures may include a Cu film having a thickness of no more than 20 nm. In some embodiments, such Cu nanostructures may include a Cu nanofoam having a porous wall having a thickness of no more than 20 nm. In some embodiments, such Cu nanostructures may include a Cu grid having a wire having a thickness of no more than 20 nm.

[0172] (i) Cu nanoparticles (“NPs”)

[0173] Fig.16 The structural design of Cu core nanoparticles is shown, wherein the diameter of the Cu core nanoparticles is no greater than 20 nm and has LaF3 or La 1-x Ba x F 3-x Coating / Shell. Fig.16 In the embodiment, due to the spherical shape of the Cu core nanoparticles, their thickness / diameter in any direction is no more than 20 nm.

[0174] Synthesis of Cu Nanoparticles (“NPs”)

[0175] NH4OH (0.5 mL, 14.5 M) was added to a stirred solution of CuCl2·2H2O (0.24 g, 1.4 mmol) and cetrimide (CTAB, 0.68 g, 1.87 mmol) in water (93 mL, DI) at 23°C in an argon atmosphere. Hydrazine hydrate (50-60%, 3 mL, 17.66 M) was added to a solution of CTAB (0.68 g, 1.87 mmol) and citric acid monohydrate (0.036 g, 0.18 mmol) in water (57 mL, DI). The hydrazine solution was immediately transferred to a 60 mL syringe and added to the Cu precursor solution via a syringe pump over 5 minutes. Once the addition of the hydrazine solution was complete, the argon line was removed and the reactants were stirred under open air. Once exposed to air, a solution of citric acid monohydrate (0.21 g, 1.0 mmol) in water (5 mL) was injected once. The mixture was then stirred under open air for 1 hour. The Cu NPs were separated by centrifugation (12,000 rpm, 5 min), the supernatant was discarded, and the Cu NPs were washed twice with ethanol (10 mL). Fig.17 As shown, the product shows a small broad Cu peak by XRD. The average size of the Cu nanoparticles is about 6 nm ( Fig.19A ).

[0176] Synthesis of Cu nanoparticle shell

[0177] The Cu nanoparticles (NP) (6 nm) were isolated and washed once with water (20 mL). The Cu NPs were redispersed in water (300 mL), a solution of La(NO3)3 6H2O (0.43 g, 1.0 mmol) in water (60 mL) was added, and the mixture was stirred in an argon atmosphere (60 min). The sample was separated (12,000 rpm, 10 min) and redispersed in water (300 mL). A solution of NaF (0.042 g, 1.0 mmol) in water (60 mL) was injected into the stirred solution at 6 mL / min and stirred in an argon atmosphere (60 min). The sample was separated by centrifugation (12,000 rpm, 10 min) and washed twice with ethanol (20 mL). XRD showed that the Cu core sample with LaF3 shell was completely oxidized to Cu2O. See Fig.18 . Fig.19A and 19B TEM images of 6 nm Cu core NPs and 6 nm Cu core NPs with LaF 3 shell are depicted, respectively.

[0178] Reduction of Cu2O to Cu in 6 nm Cu core NPs with LaF3 shell.

[0179] The Cu2O in the core nanoparticles was effectively reduced to Cu by thermal treatment in a gas mixture of H2 and N2 at 300 °C for 6 h. The particle size of the Cu NPs increased during the reduction reaction.

[0180] (ii) Cu nanowires (“NWs”) encapsulated in LaF 3 or Ba-doped LaF 3 shells (“hard shells”).

[0181] Fig.21 The structural design of Cu core nanowires is shown, wherein the cross-sectional diameter of the Cu nanowires is no greater than 20 nm and has LaF3 or La 1-x Ba x F 3-x Coating. Fig.21 wherein the cross-sectional diameter of the Cu core in the nanowire is no greater than 20 nm, and La 1-x Ba x F 3-x Or the thickness of the LaF3 shell / coating is about 5 nm.

[0182] Two-phase shell formation on copper nanowires

[0183] About 20 mg of Cu nanowires were dispersed in 50 ml of toluene. The first portion of tetrabutylammonium bromide (0.322 g, 1.0 mmol) was added to the Cu nanowire toluene suspension. A solution of La(NO3)3 6H2O (0.866 g, 2.0 mmol) in water (50 mL) was injected into the toluene suspension at 5 mL / min. The mixture was stirred very quickly for 2 hours. The water layer was removed by a separatory funnel and a second portion of tetrabutylammonium bromide (0.322 g, 1.0 mmol) was added to the toluene layer. A solution of NaF (0.084 g, 2.0 mmol) in water (50 mL) was injected into the stirred toluene suspension at 5 mL / min. The mixture was stirred very quickly for another 2 hours. The water layer was removed by a separatory funnel and ethanol (20 mL) was added to distribute the product. The product was separated by centrifugation (12,000 rpm, 10 min) and washed twice with ethanol (20 mL).

[0184] As described above, the two-phase shell formation method can be applied to nanowires. However, the application of the same coating method is not limited to nanowires. Furthermore, the core material is not limited to copper.

[0185] Fig.23A and Fig. 23B TEM images of Cu nanowires without shells are shown. Fig.24 Depicted are the XRD spectra of Cu nanowires, a small amount of Cu2O after shell formation, and the LaF3 shell of Cu nanowires. Fig.25A and 25BDepicted are SEM images of Cu nanowires before and after the formation of the two-phase LaF3 shell, respectively. Fig.26A , 26B TEM images of different magnifications in 26C show the formation of LaF3 shells around Cu nanowires. In the images, the gray area surrounding the Cu nanowires is the LaF3 shell.

[0186] Fig. 27 The electrode made of Cu nanowires encapsulated in LaF3 shell (CuNW@LaF3) is shown to be superior to Ag / Ag + Voltage curves of the charge-discharge cycles of the reference electrodes. Fig.35 The capacity of the electrode made of CuNW encapsulated in LaF3 shell reached 183 mAh / g, which is comparable to Cu@La 1-x Ba x F 3-x The capacity of the electrode made of Cu nanowires encapsulated in LaF3 shells is 95.2 mAh / g and 50.2 mAh / g for Cu@LaF3. 1-x Ba x F 3-x The capacity of CuNW@LaF3 is almost twice that of CuF2 and almost four times that of Cu@LaF3. Without wishing to be bound by any particular theory, it is believed that the amount of CuF2 formed directly determines the capacity of the battery. The more CuF2 formed, the higher the battery capacity that can be achieved. Therefore, the utilization of Cu can be significantly improved by combining Cu nanowires with LaF3 encapsulation. In one embodiment, CuNW@LaF3 can achieve about 35% of the theoretical capacity of CuF2, while Cu@La 1-x Ba x F 3-x and Cu@LaF3 can reach about 18% and 9.5% of the theoretical capacity of CuF2, respectively. Fig.36 ).

[0187] Fig.28 XRD spectra of CuNW@LaF3 are shown in the initial condition (i.e. in the electrode before use) and then after charging (fluorination) and subsequent discharge (defluorination). CuF2 can be formed after charging and then reduced to Cu after discharge. Fig.28 It is shown that Cu in nanowire form combined with LaF3 shell can circulate in liquid electrolyte.

[0188] (iii) Cu nanotubes

[0189] Fig.31 The structural design of Cu nanotubes is shown, wherein the Cu nanotubes have a Cu inner wall with a cross-sectional thickness of no more than 20 nm and LaF3 or La1-x Ba x F 3-x Coating. Fig.31 In the embodiment, the cross-sectional thickness of the Cu inner wall of the nanotube is no more than 20 nm.

[0190] (iv) Cu nanosheets and nanosheets with a thickness of no more than 20 nm

[0191] Cu flakes can have many shapes, such as triangle, rectangle, square, circle, oval, etc. Fig.32 The structure of the Cu nanosheet is shown, wherein the minimum thickness of the copper nanosheet is no more than 20 nm and the copper nanosheet has LaF3 or La 1-x Ba x F 3-x Coating. Fig.32 In the embodiment, the thickness of the Cu nanosheets in at least one direction or one axis is not greater than 20 nm. Fig.32 The structural design of the Cu nanosheet is also shown, wherein the thickness of the Cu nanosheet in the shortest direction is no more than 20 nm.

[0192] (v)Cu nanoframe

[0193] Fig.33 The structural design of the hollow Cu nanoframe is shown, wherein the Cu nanoframe has a Cu inner layer with a thickness of no more than 20 nm. Fig.33 In the embodiment, the thickness of the inner copper wall in the Cu nanoframe is not greater than 20 nm.

[0194] In the present disclosure, the metal nanostructures suitable for manufacturing the cathode electrode are not limited to copper. Figure 1B As shown, transition metals and any salts thereof can be used to make nanostructures encapsulated in various coatings as disclosed in the previous sections. Suitable transition metals include metals in the d-zone of the periodic table, including lanthanides and actinides. Transition metal salts include, but are not limited to, salts of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, hafnium, tantalum, tungsten, rhenium, osmium, iridium, platinum, gold, mercury, actinium, thorium, protactinium, uranium, neptunium, plutonium, americium, curium, berkelium, californium, einsteinium, fermium, mendelevium, nobelium and lawrencium.

[0195] Example 3. Electrochemically active structures encapsulated in self-assembled shells ("soft shells"). Fig.37A An exemplary electrochemically active structure 11 according to aspects of the present disclosure is shown. Fig.37AAs shown, the electrochemically active structure 11 may include a core 12 as described herein and a monolayer 13 comprising a shell material as described herein. According to some aspects, the monolayer 13 may be, for example, a self-assembled monolayer (SAM) comprising a surfactant as described herein. It should be understood that in this example, the monolayer 13 corresponds to the shell as described herein.

[0196] Fig.37B An exemplary electrochemically active structure 11 is shown comprising a core 12 as described herein and a monolayer 13 comprising a shell material as described herein. Fig.37B Also shown is a second monolayer 14 covering at least a portion of the first monolayer 13. The second monolayer 14 may also be the same or a different SAM as the first monolayer 13. It should be understood that in this example, the first monolayer 13 and the second monolayer 14 may together correspond to a shell as described herein. In addition, the first monolayer and the second monolayer may be self-assembled.

[0197] Fig.37C An exemplary electrochemically active structure 11 is shown comprising a core 12 as described herein and a monolayer 13 comprising a shell material as described herein. Fig.37C Also shown is a polymer layer 15 covering at least a portion of the monolayer 13. The polymer layer 15 may comprise any polymer described herein. It should be understood that in this example, the monolayer 13 and the polymer layer 15 may together correspond to a shell as described herein.

[0198] It should be understood that although Fig.37A -C shows some exemplary shell configurations, and the electrochemically active structure can include shells with different configurations. For example, the shell can include more than two SAMs and / or more than one polymer layer, wherein the positions of the SAMs and / or polymer layers are any arrangement relative to each other.

[0199] According to some aspects, the shell can be configured to accommodate changes in volume of the electrochemically active material between charged and discharged states. For example, Fig.38 An exemplary schematic diagram of charging and discharging an electrochemically active structure 21 as described herein is shown. Fig.38 As shown, the electrochemically active structure 21 may include a core 22 as described herein and a shell 23 comprising a SAM and a polymer layer 24. The core may include any core as described herein, such as a Cu core. Fig.38 For example, in F - Schematic diagram of charging the electrochemically active structure 21 when ions travel to the cathode containing the electrochemically active structure 21. Fig.38 As shown, F -Ions can traverse the shell to the core 22 to convert at least a portion of the Cu core 22 into CuF2 25. As the Cu in the Cu core 22 is converted into CuF2 25, the volume of the core can expand. Without wishing to be bound by theory, as the volume of the core expands, the SAM 23 may become defective or cracked to accommodate the change in volume. Fig.38 As shown, when the electrochemically active structure 21 is discharged, the CuF2 25 can be reduced back to Cu 22, and the volume of the core can shrink. As the volume shrinks, the SAM 23 can self-assemble or "self-repair" back to its original configuration.

[0200] For example, Cu nanowires can be encapsulated in a surfactant soft shell. The soft shell can contain at least one organic surfactant. Examples of suitable surfactants include oleylamine, oleic acid, tris(trimethylsilyl)silane, 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecanethiol, 2-(trifluoromethoxy)-benzenethiol, P-[12-(2,3,4,5,6-pentafluorophenoxy)dodecyl]-phosphonic acid, P-(3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl)-phosphonic acid, pentafluorobenzylphosphonic acid, perfluorododecanoic acid and combinations thereof. More specifically, the suitable surfactant is selected from oleylamine, oleic acid, tris(trimethylsilyl)silane or a combination thereof. In addition to the shell being made of a surfactant, the structure of the CuNW@ soft shell is similar to Fig.21 structure.

[0201] According to some aspects, the surfactant soft shell may include an organic or organic molecule-containing polymer to form a polymer shell; except that the surfactant soft shell 13 includes one or more polymers, the structure of the CuNW@ soft shell including the polymer is similar to Fig.37A The structure of CuNW@softshell with polymer shell is similar to Fig.37B , 37C and 38. According to some aspects, Fig.37C may represent a cross section of a CuNW, and the monolayer 13 and the polymer layer 15 may together correspond to a shell as described herein. Fig.37C In some aspects of the present invention, the monolayer 13 and the polymer layer 15 may correspond to a surfactant shell and a polymer shell, respectively. Fig.37CCertain exemplary shell configurations are shown as described for CuNWs, but the shell can include different configurations. For example, the shell can include a surfactant shell and a polymer shell in different arrangements. For example, the shell can include more than one surfactant shell and more than one polymer shell, wherein the surfactant shell and the polymer shell are positioned in any arrangement relative to each other.

[0202] For example, a solution of CuCl2 2H2O (85 mg, 0.5 mmol) in oleylamine (5 g, 18.7 mmol) and oleic acid (0.1 g, 0.354 mmol) was sonicated in a glass vial until it was completely dissolved. Tris(trimethylsilyl)silane (0.5 g, 2.0 mmol) was added and the mixture was heated to 120°C until the dark blue solution turned into a clear yellow. The mixture was further heated to 165°C for 18 h. Copper nanowires were formed. The Cu nanowires were separated by centrifugation (12,000 rpm, 10 min) and washed 3 times with toluene (10 mL). Fig. 22 , Fig.23A and Fig. 23B The XRD spectrum and TEM image of the Cu nanowires produced in this example are shown respectively.

[0203] About 20 mg of Cu nanowires were redispersed in 50 ml of toluene. The first portion of tetrabutylammonium bromide (0.322 g, 1.0 mmol) was added to the Cu nanowire toluene suspension. A solution of La(NO3)3 6H2O (0.866 g, 2.0 mmol) in water (50 mL) was injected into the toluene suspension at 5 mL / min. The mixture was stirred very quickly for 2 hours. The water layer was removed by a separatory funnel and a second portion of tetrabutylammonium bromide (0.322 g, 1.0 mmol) was added to the toluene layer. A solution of NaF (0.084 g, 2.0 mmol) in water (50 mL) was injected into the stirred toluene suspension at 5 mL / min. The mixture was stirred very quickly for another 2 hours. The water layer was removed by a separatory funnel and ethanol (20 mL) was added to distribute the product. The product was separated by centrifugation (12,000 rpm, 10 min) and then washed twice with ethanol (20 mL).

[0204] Fig. 22 and Fig.24 The XRD spectra of Cu nanowires, a small amount of Cu2O after shell formation, and the LaF3 shell of Cu nanowires are depicted, respectively. Fig.25A and 25B Depicted are SEM images of Cu nanowires before and after the formation of the two-phase LaF3 shell, respectively. Fig.26A , 26BTEM images of different magnifications in 26C show the formation of LaF3 shells around Cu nanowires. In the images, the gray area surrounding the Cu nanowires is the LaF3 shell.

[0205] The LaF3 shell may contain Ba doping. Fig.34 and Fig.35 The capacity improvement achieved after Ba doping according to some aspects of the present disclosure is shown. Fig.34 Cu@LaF3 electrode or Cu@Ba x La 1-x F 3-x Electrode compared to Ag / Ag + Referring to the voltage curve of the first charge-discharge cycle of the electrode, the capacity delivery of the Ba-doped electrode reaches 95.2 mAh / g, compared with only 50.2 mAh / g for Cu@LaF3 ( Fig.35 ). Thus, Ba doping of the LaF3 shell almost doubles the capacity. The use of Ba doping improves the ionic conductivity of the LaF3 shell (see Fig.35 ). With Ba doping, fluoride ions can more easily pass through the shell to react with Cu to form CuF2, and the amount of CuF2 formed directly determines the capacity of the battery. The more CuF2 is formed, the higher the capacity of the battery. Therefore, the utilization of Cu can be almost doubled by Ba doping of the LaF3 shell.

[0206] Fig.28 XRD spectra of CuNW@LaF3 are shown in the initial condition (i.e. in the electrode before use) and then after charging (fluorination) and subsequent discharge (defluorination). CuF2 can be formed after charging and then reduced to Cu after discharge. Fig.28 The data in show that Cu in nanowire form bound to LaF3 shells can be reversibly cycled in liquid electrolytes.

[0207] The cathode electrode was prepared using CuNW@soft shell nanomaterials. The average cross-sectional diameter of the CuNW core was about 20 nm. The voltage curve of the charge-discharge cycle of the CuNW@soft shell electrode is shown in Fig.29 In. Use Ag / Ag + The electrode serves as a reference in the experiment. Fig.29 The capacity of the 20nm CuNW@ soft shell cathode can reach more than 200mAh / g. The CuNW@ soft shell electrode was further characterized by XRD, and the experimental results are shown in Fig.30 middle. Fig.30The XRD spectra of CuNW@soft shell after charging (fluorination) and subsequent discharge (defluorination) are shown respectively. CuF2 can be formed after charging and then reduced to Cu after discharge. XPS spectral data of core@shell nanoparticles containing Cu (64.83%), La (14.68%), Ba (0.28%), F (20.21%) (wherein the shell itself contains La (41.75%), Ba (0.79%), F (57.46%)) confirm that the nanoparticles are Cu@La 0.97 Ba 0.03 F 2.97 Cu@LaF3 and Cu@La 0.97 Ba 0.03 F 2.97 The XRD spectrum is shown in Fig.46 middle.

[0208] Example 4. Comparison of cathodes made of Cu nanostructures. A series of cathodes with Cu nanostructures have been prepared for F-shuttle cells. The Cu nanostructures used in the preparation of the cathodes are CuNP@LaF3 with a core having an average diameter of about 50 nm, CuNP@LaF3 with a core having an average diameter of about 50 nm, and CuNP@LaF3 with a core having an average diameter of about 50 nm. 0.97 Ba 0.03 F 2.97 , CuNW@LaF3 with a core having an average cross-sectional diameter of about 20 nm, and CuNW@soft shell with an average cross-sectional diameter of about 20 nm.

[0209] Fig.34 The voltage curves of the charge-discharge cycles of various electrodes are shown, including CuNP@LaF3 with a thickness of about 50 nm, CuNP@La 0.97 Ba 0.03 F 2.97 , CuNW@LaF3 of about 20nm and CuNW@soft shell of about 20nm. + The electrode serves as a reference in the experiment. Fig.34 The capacity of 20 nm Cu nanowires encapsulated in LaF3 shell or surfactant soft shell is significantly higher than that of Cu nanowires encapsulated in LaF3 or La 0.97 Ba 0.03 F 2.97 Capacity of 50 nm Cu nanowires in the shell.

[0210] like Fig.35 As shown, the CuNP@LaF3 with a thickness of 50 nm and the CuNP@La 0.97 Ba 0.03 F 2.97The capacities of the electrodes made of 20 nm CuNW@LaF3 and 20 nm CuNW@soft shell are 50.2, 95.2, 183 and 203 mAh / g, respectively. Therefore, the electrodes made of Cu nanowires encapsulated in LaF3 shell or soft shell are CuNP@LaF3 and CuNW@soft shell. 0.97 Ba 0.03 F 2.97 The capacity of CuNP@LaF3 is almost twice that of CuNP@LaF3. In comparison, the theoretical capacity of an electrode made of CuF2 is about 528 mAh / g.

[0211] right Fig.35 The capacity of the cathodes in the experiment was normalized to the theoretical capacity of CuF2 to obtain the percentile capacity of each electrode. Fig.36 The percentile capacities of all electrodes tested are shown. Fig.36 It is shown that the capacity of electrodes made of 20 nm Cu nanowires encapsulated in LaF3 shell and surfactant soft shell can reach 34.7% and 38.4% of the theoretical capacity of CuF2, respectively.

Claims

1. A fluoride ion battery comprising: an anode comprising an alkaline earth metal, a rare earth metal, or a combination thereof, and having an outer solid electrolyte interphase layer; a cathode comprising a cathode core comprising a transition metal, a lanthanide, an actinide, or a combination thereof and a fluoride-containing shell at least partially surrounding the cathode core, wherein the fluoride-containing shell comprises a first metal and a second metal, and the first metal is barium; and a liquid electrolyte comprising fluoride ions between the anode and the cathode; wherein the outer solid electrolyte interphase layer is covalently connected to the anode, and the outer solid electrolyte interphase layer comprises CF3(CF2)5CH2, CF3(CF2)2CH2, p-tert-butylphenyl, p-methoxyphenyl, p-(dimethylamino)phenyl, p-nitrophenyl, p-trifluoromethylphenyl, or a combination thereof; Alternatively, the outer solid electrolyte interphase layer comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene, 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof.

2. The fluoride ion battery according to claim 1, wherein the liquid electrolyte comprises bis(2-methoxyethyl) ether, bis(2,2,2-trifluoroethyl) ether, N,N,N-trimethyl-N-neopentylammonium fluoride, N,N-dimethyl-N,N-dineopentylammonium fluoride, propionitrile or a combination thereof.

3. The fluoride ion battery of claim 1, wherein the cathode core has at least one dimension less than or equal to 25 nm.

4. The fluoride ion battery of claim 1, wherein the cathode core comprises a transition metal selected from the group consisting of copper, iron, lead, bismuth, cobalt, alloys thereof, fluorides thereof, and combinations thereof.

5. The fluoride ion battery of claim 1, wherein the anode is an alkaline earth metal selected from calcium, and the rare earth metal is selected from cerium and lanthanum.

6. The fluoride ion battery of claim 1, wherein the second metal is a transition metal, an alkali metal, an alkaline earth metal, a Group 3 element, a Group 13 element, or a combination thereof.

7. The fluoride ion battery of claim 1, wherein the second metal is a lanthanide, an actinide, or a combination thereof.

8. The fluoride ion battery of claim 1, wherein the fluoride-containing shell comprises La 1-x Ba x F 3-x , where X = 0.03-0.

5.

9. The fluoride ion battery of claim 1, wherein the fluoride-containing shell comprises La 1-x Ba x F 3-x , where X = 0.

03.

10. The fluoride ion battery of claim 1, wherein the average thickness of the fluoride-containing shell is no greater than 5 nm.

11. A fluoride ion battery comprising: an anode comprising an alkaline earth metal, a rare earth metal, or a combination thereof, and having an outer solid electrolyte interphase layer; a cathode comprising an electrochemically active structure having a core and a shell at least partially surrounding the core, wherein the shell comprises a shell material comprising one or more organic molecules having one or more functional groups; and a liquid electrolyte comprising fluoride ions between the anode and the cathode; wherein the outer solid electrolyte interphase layer is covalently connected to the anode, and the outer solid electrolyte interphase layer comprises CF3(CF2)5CH2, CF3(CF2)2CH2, p-tert-butylphenyl, p-methoxyphenyl, p-(dimethylamino)phenyl, p-nitrophenyl, p-trifluoromethylphenyl, or a combination thereof; Alternatively, the outer solid electrolyte interphase layer comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene, 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof.

12. The fluoride ion battery of claim 11, wherein the liquid electrolyte comprises bis(2-methoxyethyl)ether, bis(2,2,2-trifluoroethyl)ether, N,N,N-trimethyl-N-neopentylammonium fluoride, N,N-dimethyl-N,N-dineopentylammonium fluoride, propionitrile, or a combination thereof.

13. The fluoride ion battery of claim 11, wherein the core has at least one dimension less than or equal to 25 nm.

14. The fluoride ion battery of claim 11, wherein the core comprises a transition metal selected from the group consisting of copper, iron, lead, bismuth, cobalt, alloys thereof, fluorides thereof, and combinations thereof.

15. The fluoride ion battery of claim 11, wherein the alkaline earth metal is calcium and the rare earth metal is selected from cerium and lanthanum.

16. The fluoride ion battery according to claim 11, wherein the one or more functional groups are selected from: -COOH, -NH2, -COH, -OH, -SH, -PO3H, -SO3H, -CN, -NC, -COO - , enediol, -N≡N + (BF4 - )、-Sac、-CSSH、-S2O3 - Na + 、-SeH、-PO3 2- / -P(O)(OH)2、-PO4 2- , -SiH3, -SiCl3, -OCH2CH3, formula (I), formula (II), formula (III), alkanes, alkynes, alkenes, aromatic rings and combinations thereof, Wherein formula (I) is: Formula (II) is: And formula (III) is: wherein R' and R" are each independently an organic chain, or an aryl group, a partially or fully fluorinated aryl group, alone or in combination with another R' or R".

17. The fluoride ion battery according to claim 11, wherein the one or more functional groups are selected from: -COOH, -NH2, -COH, -OH, -SH, -PO3H, -SO3H, -CN, -NC, -COO - , enediol, -N≡N + (BF4 - )、-Sac、-CSSH、-S2O3 - Na + 、-SeH、-PO3 2- / -P(O)(OH)2、-PO4 2- , -SiH3, -SiCl3, -OCH2CH3, formula (I), formula (II), formula (III), alkanes, alkynes, alkenes, aromatic rings and combinations thereof, Wherein formula (I) is: Formula (II) is: And formula (III) is: wherein R' and R" are each independently a partially or fully fluorinated organic chain, or an aryl group, a partially or fully fluorinated aryl group, alone or in combination with another R' or R".

18. The fluoride ion battery according to claim 16 or 17, wherein the one or more functional groups are selected from: -HC=CH2, -C≡CH and combinations thereof.

19. The fluoride ion battery according to claim 16 or 17, wherein R' and R" are selected from (CF2) n CF3, (CH2CF2) n CF3 and (CF2CH2O) n CF3.

20. The fluoride ion battery according to claim 16 or 17, wherein formula (III) is the following structure:

21. The fluoride ion battery according to claim 20, wherein formula (IV) is the following structure:

22. A fluoride ion battery comprising: an anode comprising an alkaline earth metal, a rare earth metal, or a combination thereof, and having an outer solid electrolyte interphase layer; a cathode comprising an electrochemically active structure having a core and a shell at least partially surrounding the core, wherein the shell comprises a shell material comprising an organic molecule; and a liquid electrolyte comprising fluoride ions between the anode and the cathode; wherein the outer solid electrolyte interphase layer is covalently connected to the anode, and the outer solid electrolyte interphase layer comprises CF3(CF2)5CH2, CF3(CF2)2CH2, p-tert-butylphenyl, p-methoxyphenyl, p-(dimethylamino)phenyl, p-nitrophenyl, p-trifluoromethylphenyl, or a combination thereof; Alternatively, the outer solid electrolyte interphase layer comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene, 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof.

23. The fluoride ion battery of claim 22, wherein the liquid electrolyte comprises bis(2-methoxyethyl)ether, bis(2,2,2-trifluoroethyl)ether, N,N,N-trimethyl-N-neopentylammonium fluoride, N,N-dimethyl-N,N-dineopentylammonium fluoride, propionitrile, or a combination thereof.

24. The fluoride ion battery of claim 22, wherein the core has at least one dimension less than or equal to 25 nm.

25. The fluoride ion battery of claim 22, wherein the core comprises a transition metal selected from the group consisting of copper, iron, lead, bismuth, cobalt, alloys thereof, fluorides thereof, and combinations thereof.

26. The fluoride ion battery of claim 22, wherein the alkaline earth metal is calcium and the rare earth metal is selected from cerium and lanthanum.

27. The fluoride ion battery of claim 22, wherein the organic molecule is an organic surfactant selected from the group consisting of oleylamine, oleic acid, tris(trimethylsilyl)silane, 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecanethiol, 2-(trifluoromethoxy)-benzenethiol, P-[12-(2,3,4,5,6-pentafluorophenoxy)dodecyl]-phosphonic acid, P-(3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl)-phosphonic acid, pentafluorobenzylphosphonic acid, perfluorododecanoic acid, and combinations thereof.

28. The fluoride ion battery according to claim 22, wherein the organic molecule is an organic surfactant comprising one or more functional groups selected from the group consisting of: -COOH, -NH2, -COH, -OH, -SH, -PO3H, -SO3H, -CN, -NC, -COO - , enediol, -N≡N + (BF4 - )、-Sac、-CSSH、-S2O3 - Na + 、-SeH、-PO3 2- / -P(O)(OH)2、-PO4 2- , -SiH3, -SiCl3, -OCH2CH3, formula (I), formula (II), formula (III), alkanes, alkynes, alkenes, aromatic rings and combinations thereof, Wherein formula (I) is: Formula (II) is: And formula (III) is: wherein R' and R" are each independently an organic chain, or an aryl group, a partially or fully fluorinated aryl group, alone or in combination with another R' or R".

29. The fluoride ion battery according to claim 22, wherein the organic molecule is an organic surfactant comprising one or more functional groups selected from the group consisting of: -COOH, -NH2, -COH, -OH, -SH, -PO3H, -SO3H, -CN, -NC, -COO - , enediol, -N≡N + (BF4 - )、-Sac、-CSSH、-S2O3 - Na + 、-SeH、-PO3 2- / -P(O)(OH)2、-PO4 2- , -SiH3, -SiCl3, -OCH2CH3, formula (I), formula (II), formula (III), alkanes, alkynes, alkenes, aromatic rings and combinations thereof, Wherein formula (I) is: Formula (II) is: And formula (III) is: wherein R' and R" are each independently a partially or fully fluorinated organic chain, or an aryl group, a partially or fully fluorinated aryl group, alone or in combination with another R' or R".

30. The fluoride ion battery according to claim 28 or 29, wherein the organic molecule is an organic surfactant comprising one or more functional groups selected from the group consisting of: -HC=CH2, -C≡CH, and combinations thereof.

31. The fluoride ion battery according to claim 28 or 29, wherein R' and R" are selected from (CF2) n CF3, (CH2CF2) n CF3 and (CF2CH2O) n CF3.

32. The fluoride ion battery according to claim 28 or 29, wherein formula (III) is the following structure:

33. The fluoride ion battery according to claim 32, wherein formula (IV) is the following structure:

34. A fluoride ion battery comprising: an anode comprising an alkaline earth metal, a rare earth metal, or a combination thereof, and having an outer solid electrolyte interphase layer; a cathode comprising an electrochemically active structure having a core and a shell at least partially surrounding the core, wherein the shell comprises a polymer; and a liquid electrolyte comprising fluoride ions between the anode and the cathode; wherein the outer solid electrolyte interphase layer is covalently connected to the anode, and the outer solid electrolyte interphase layer comprises CF3(CF2)5CH2, CF3(CF2)2CH2, p-tert-butylphenyl, p-methoxyphenyl, p-(dimethylamino)phenyl, p-nitrophenyl, p-trifluoromethylphenyl, or a combination thereof; Alternatively, the solid electrolyte interphase layer comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene, 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof.

35. The fluoride ion battery of claim 34, wherein the polymer is an oligomer.

36. The fluoride ion battery of claim 34 or 35, wherein the liquid electrolyte comprises bis(2-methoxyethyl)ether, bis(2,2,2-trifluoroethyl)ether, N,N,N-trimethyl-N-neopentylammonium fluoride, N,N-dimethyl-N,N-dineopentylammonium fluoride, propionitrile, or a combination thereof.

37. The fluoride ion battery of claim 34 or 35, wherein the core has at least one dimension less than or equal to 25 nm.

38. The fluoride ion battery of claim 34 or 35, wherein the core comprises a transition metal selected from the group consisting of copper, iron, lead, bismuth, cobalt, alloys thereof, fluorides thereof, and combinations thereof.

39. The fluoride ion battery of claim 34 or 35, wherein the alkaline earth metal is calcium and the rare earth metal is selected from cerium and lanthanum.

40. The fluoride ion battery of claim 34 or 35, wherein the shell comprises a polymer selected from the group consisting of polyvinylpyrrolidone, poly(methyl methacrylate), and combinations thereof.

Citation Information

Patent Citations

  • Barium-doped composite electrode materials for fluoride-ion electrochemical cells

    US11177512B2

  • Composite electrode materials for fluoride-ion electrochemical cells

    US11251420B2

  • Cannula ring and related systems and methods

    US20130150654A1

  • Non-aqueous fluoride salts, solutions, and their uses

    US20170062874A1

  • Cannula ring and related systems and methods

    US20190314612A1